GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 537890617 species occurrences available in GBIF matching the query: All data. The dataset includes 537890617 records from 13120 constituent datasets: 431 records from Bee specimens. 1576 records from MfN - Trace fossils. 27 records from Schulgarten Am Hafen. 4960 records from NRM-Herpetology. 46 records from Liether Park (LMS), 5a. 3 records from MSB Mammal Observations (Arctos). 1 records from Damaeus concolor. 8579 records from The atlas of breeding birds in Małopolska. 70738 records from University of Alberta Vascular Plant Herbarium (ALTA). 745 records from (Table 2) Benthic foraminifers at DSDP Hole 72-518. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 37820 records from Belgian Coccinellidae - Ladybird beetles in Belgium (INBO subset). 39 records from Colección de Urocordados. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 987 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Thraupidae. 82 records from Mainfränkischer Trockenrasen und Naturschutzgebiet Höhfeldplatte bei Veitshöchheim. 36 records from Selz (Ingelheim am Rhein). 16 records from Im und um das Schulhaus. 5 records from Streuobstwiesengebiet (Kreis Ahrweiler). 1 records from 5. Wiener Gemeindebezirk. 106428 records from Jordal. 371 records from Bannwald Burghauser Forst. 742 records from Paleogene dinoflagellates from Thyra-O-Formation, eastern North Greenland. 46 records from Smear slide analysis on sediment core GeoB4216-1. 103 records from Ostracoda abundance of Hole 24-237. 8 records from Nannofossil abundance of Hole 49-412A. 9 records from Nannofossil abundance of Hole 26-250. 48 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-703. 2167 records from BIOTA Southern Africa - The Collection of Lichens at the Botanische Staatssammlung München. 3726 records from (Table 3) Relative abundance of benthic foraminifera in sediment profile HUD84-030-04. 180 records from (Table 7) Distribution of the large, many-chambered Globigerinelloides species in DSDP Hole 79-545. 52 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE255. 99 records from (Table 4) Numerical abundances of nannofossil taxa in ODP Hole 126-792A. 17 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE258. 812 records from Planktic foraminifera abundance of Hole 94-607. 67 records from Hertfordshire Biological Records Centre - Roadside Verge Survey 1986 (Herts data from Cambs WT survey). 15181 records from British Lichen Society - BLS Lichen Database: Welsh churchyards. 6 records from (Table 1) Abundance of ciliates, dinoflagellates, nauplii and krill at different stations in the Godthabsfjord. 234 records from (Table T4) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1211B, Shatsky Rise, Pacific Ocean. 66722 records from SANT herbarium vascular plants collection. 3 records from First report of the genus Conostigmus Dahlbom (Hymenoptera: Ceraphronoidea: Megaspilidae) from India with description of a new species. 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 318 records from A taxonomic review of the genus Azteca (Hymenoptera: Formicidae) in Costa Rica and a global revision of the aurita group.. 6855 records from Echinoderm collection of National Museum of Nature and Science. 31 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 376 records from Porpoises (NRM). 58475 records from Oregon State University Herpetological Collection. 4 records from New data on recently described rodent species Paulina's Limestone Rat Saxatilomys paulinae Musser, Smith, Robinson & Lunde, 2005 (Mammalia: Rodentia). 3592 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Invasive Insecta. 3 records from Fossil occurrence of calcareous nannofossils from IODP Hole 319-C0009A. 44 records from Solanum_baretiae. 1 records from A record of Anzygina billi Fletcher & Larivière, 2009 (Hemiptera: Cicadellidae) from New Zealand. 2000 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 496530 records from Field Museum of Natural History (Zoology) Bird Collection. 1 records from Ctenophora ZMK. 26 records from Schwedische Oribatei (Acari). III.. 335 records from Meiofaunal abundance in sediments obtained during RRS Discovery cruise D297. 5043 records from RSPB - Dartford Warbler national surveys in the UK (SCARABBS). 1 records from Report on the occurrence of synanthropic derived form of Chrysomya megacephala (Diptera: Calliphoridae) from Royapuram fishing harbour, Chennai, Tamil Nadu, India. 1 records from Pollen analysis of sediment profile BLA00 from Blankensee. 62 records from Tag der Artenvielfalt BUND Kaiserslautern. 99 records from Dorfrand Mauderode. 163 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 70111 records from Kyushu University Museum Coleoptera Collection. 2754 records from (Table 7) Benthic foraminifera in middle-late Miocene sediments of DSDP Site 90-590. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 (Araneae, Tetragnathidae) with notes on habits and conservation status . 123 records from Birdrace-Thüringer_Becken-Sömmerda. 57 records from Waldhusener Moor (Lübeck-Kücknitz). 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 245 records from Gieselbachtal Fulda-Harmerz. 24 records from Ornithologische Wanderung um Tussenhausen. 2 records from Hildener Heide - Spörkelnbruch (Haan). 97 records from BIRDRACE NABUhu Trier!. 101 records from BIRDRACE Enger am Spektiv. 79186 records from All Ireland Non-Marine Molluscan Database. 77 records from Faunal assemblage of sediment core GS7603-12. 72 records from Faunal assemblage of sediment core TR149-35. 95 records from Nematode densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC09. 53 records from Plasm bearing foraminifera counts from M35/1_MSN1058. 299 records from Total foraminifera counts of multinet M21/3_MSN662. 150 records from Total foraminifera counts of multinet M42/3_MSN1361. 90 records from Plasm bearing foraminifera counts of multinet M21/2_MSN639. 6 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 2421 records from Census of plant species in Toffo forest reserve. 157 records from Abundance of planktic foraminifera at CTD station PS55/063. 31 records from Benthic foraminifera counts of sediment core PS2644-2. 407 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Buchaugraben in the Lower Inn Valley area. 68 records from Abundance of dead benthic foraminifera in sediment core CD86_01_BC1. 58 records from Abundance of living benthic foraminifera in sediment core CD86_04_BC4. 918 records from (Fig. 4) Assemblage of benthic foraminifera in sediment core GeoB6725-1. 152 records from Faunal assemblage of sediment core TR149-38b. 96 records from Total foraminifera counts from multinet M31/2_MSN894. 169 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 45 records from Total foraminifera counts of multinet M21/4_MSN703. 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 4 records from Plasm bearing foraminifera counts of multinet PO231/3_MSN1335. 69 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1379. 153 records from Distribution of planktic foraminifera (125-250 µm) of sediment core PS1909-2. 66 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/508-22. 149 records from Abundance of planktic foraminifera at CTD station PS55/078-1. 151 records from (Appendix A) Abundance of calcareous dinoflagellates of sediment core GeoB2204-2. 1 records from Microplankton counts and carbon biomass at station TT007_7-CTD76. 14 records from Microzooplankton abundance and biomass at station NBP97-03-11-1. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-18-5. 133 records from Phytoplankton abundance at station CD46_2005C#4. 102 records from BIRDRACE Niederrheinische Bartgeier. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 24 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD11. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD85. 6 records from Microzooplankton abundance and biomass at station NBP97-03-06-8. 6 records from Microzooplankton abundance and biomass at station NBP97-08-03-3. 6 records from Microzooplankton abundance and biomass at station NBP97-08-37-4. 86 records from Distribution of the sand-ascidian Seriocarpa rhizoides in surface sediments of Josephine-Bank, North Atlantic (Table 4). 666 records from Faunal assemblage of ODP Hole 101-633A (Table 1). 6 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/323-1. 10 records from Zoobenthos in surface sediments during Professor Vodyanitskiy cruise PV32. 6 records from Abundance of radiolaria at station UT99-20-1. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 189 records from Naturpark Sternberger Seenland. 39 records from Bonner Schülerinnen am Rodder Maar. 1000 records from Plant specimens of Natural History Museum, Kishiwada City. 7857 records from MfN - Fossil plants (Mesophytic). 360 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 238 records from Coccoliths in ODP Hole 104-643A. 448 records from Geometry of coccolith Gephyrocapsa in sediment core GIK23062-1. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 1634 records from ZFMK DORSA. 2 records from Nannofossil abundance of Hole 1-6A. 3 records from Nannofossil abundance of Hole 10-93. 11 records from Nannofossil abundance of Hole 73-521A. 57245 records from Bird Observation Data. 16 records from Diversidad de Bacterias Fotótrofas en Comunidades Microbianas Bentónicas de Bahía Concepción, B.C.S. (CIBNOR). 254 records from Grünes Germersheim. 35 records from Ortsrand Zandershagen. 602 records from Fossil (NSMK-FO). 13461 records from Plant (JNHM-PL). 1019 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 13 records from (Table 3) Distribution of some benthic foraminifera in ODP Hole 108-659A. 11 records from Tab. 3: Stomach contents of Knots of Hazen Camp. 204 records from Dinoflagellates and pollen of the Brito-Arctic Igneous Province flora, ODP Hole 104-642E. 390 records from (Table 3) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Cismon core. 1470 records from (Table 10) Distribution of planktonic foraminifers in ODP Hole 108-662A. 23 records from Planktonic foraminifera in ODP Hole 112-688A (Table 1). 38 records from Pollen profile ADR353. 40 records from Pollen record of sediment core Bokanjacko Blato 1. 199307 records from Atlas Survey of the Butterflies of Denmark. 63 records from Rosarium (LMS), Klasse 6a. 3 records from Nannofossil abundance of Hole 6-48A. 2 records from Nannofossil abundance of Hole 3-17A. 11 records from Nannofossil abundance of Hole 22-218. 16 records from Nannofossil abundance of Hole 24-235. 41 records from Nannofossil abundance of Hole 24-238. 16 records from Nannofossil abundance of Hole 57-438. 30 records from Nannofossil abundance of Hole 30-285A. 13 records from Nannofossil abundance of Hole 94-606A. 15 records from Diatom abundance measured on water bottle samples at station PS58/090-4. 1966 records from Relative abundance of Neogene nannofossils at ODP Site 165-999 from the Caribbean. 1596 records from (Table 14) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-592. 18 records from Meiofauna abundance in sediment core 54301-009. 73 records from Macrofauna abundance in surface sediment sampled during cruise DI222/2. 255 records from Planktic foraminifera counts of sediment core RC09-150. 921 records from Planktic foraminifera counts of sediment core RC14-37. 480 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 163259 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 3953 records from Colección de Ostrácodos Recientes del Sur del Golfo de México (ICMyL-DF, UNAM). 1458 records from Hertfordshire Biological Records Centre - Hertfordshire Lowland Meadow Inventory Survey 2010. 2069 records from Insect (JJHA-IN). 143 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 2682 records from Foraminifera distribution of sediment core KET80-03. 4500 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 31 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part III. 212 records from (Table 3) Relative abundance of selected benthic foraminifera in ODP Hole 104-642C. 8 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE262. 871 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 87 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2008. 2387 records from Estudio de la avifauna y de las interacciones ave-planta en la Reserva de la Biosfera de la Barranca de Metztitlán Hidalgo, México. 1700 records from Nuevos registros de esponjas del Pacífico mexicano, Mar de Cortés y Archipiélago Revillagigedo. 569 records from Insectos del orden Trichoptera de la Sierra Tarahumara, Chihuahua, México. 2543 records from Diversidad y riqueza vegetal de los substratos rocosos del centro del estado de Veracruz. 18 records from Akita Prefectural Museum＋Cnidarians Specimens of Akita Prefectural Museum. 11 records from Akita Prefectural Museum＋Ascidians Specimens of Akita Prefectural Museum. 2427 records from Ibaraki Nature Museum, Mollusk collection. 578 records from (Table 3) Relative abundances of selected planktonic foraminifera of ODP Site 117-722. 940 records from Planktic foraminifera distribution of sediment core CS72-37. 716 records from Foraminifera distribution of sediment core Chain61-19. 21 records from (Table 3) Paleotemperature estimates for ODP Hole 105-646B. 12 records from Pollen data of trap CB1. 1 records from Cepheus minutus. 2079 records from (Table 15) Ranges of benthic foraminifers through the early-middle Miocene in ODP Hole 115-709A. 3655 records from Collection Anatomie Histologie - SMF. 22150 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 2 records from Nothrus palustris. 196122 records from Herbarium Berolinense. 1353 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC12-294. 10 records from UC Davis Department of Anthropology Museum. 88 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 333 records from renaturierter Main (Kemmern bei Bamberg). 15 records from Phytoplankton abundance in surface water during Akademik Vernadsky cruise AV22. 28 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100320. 22 records from Occurrence of mammalia relicts at site Castlepook Cave. 4 records from Occurrence of mammalia relicts at site Ahlen. 4 records from Planktic foraminifera abundance of Hole 19-191A. 57 records from Planktic foraminifera abundance of Hole 84-566. 432 records from Planktic foraminifera abundance of Hole 94-606A. 1344 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase 3 (Chapulhuacán y Pisaflores). 3259 records from Florística de áreas protegidas en el estado de Durango. 1 records from Hoplophora testudinea. 2940 records from RSPB - Cirl bunting national surveys in the UK (SCARABBS). 149 records from Benthic foraminiferal abundances from eight sites of the Northwest Australian shelf. 28 records from (Table 1) Mineralogy and abundance of Truncorotalia tosaensis in ODP Hole 194-1195A. 52181 records from ANTARCTIC PLANT DATABASE. 78 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Polychaetes. 84070 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1988) (AfrOBIS). 368 records from Great Lakes Forestry Centre Insect Collection. 36116 records from Fish Collection of Yokosuka City Museum. 886 records from Lepidoptera Observations from New Zealand by Donald Hobern. 9754 records from Universidad Politécnica de Madrid, Dpto. Biología Vegetal, Banco de Germoplasma. 1358 records from Electron Micrograph Database (Australian Antarctic Data Centre). 46156 records from Zooplankton in the bay of Biscay (1995-2004 Yearly spring DEPM surveys). 41646 records from Coleção Entomológica Paulo Nogueira-Neto - IB/USP. 399 records from Colecciones Zoológicas de la Universidad de León, Colección de Poliquetos. 10591 records from Planktic foraminifera (%) of sediment core MD97-2151. 53 records from Planktic foraminifera assemblage in sediment core GIK23041-1. 33 records from Planktic foraminifera assemblage in sediment core GIK17724-1. 6602 records from Relative abundance of planktic foraminifera in sediment core GeoB1309-2. 101 records from MVZ Mammal Observations (Arctos). 20 records from (Table 2) Abundance and biomass of the main microplankton biota components in the Murmansk coastal pelagic zone in March 1998. 26721 records from Bird Observational Records. 6383 records from RSPB - RSPB Reserves breeding bird surveys. 6870 records from Histroical benthic dredge samples from the southern baltic and the North Sea (EurOBIS). 14484 records from iziko South African Museum - Shark Collection (AfrOBIS). 127133 records from Fish specimens. 49 records from CNIN/Tipos Orthoptera. 1384 records from Bridel Herbar. 34506 records from Herbarium de Geo. B. Hinton, México. 22751 records from Lepidopteran specimens of Iwate Prefectural Museum. 556 records from RMT Trawl catch from 1985/86 V1 ADBEX III voyage. 7 records from Analyses of the recent components of sediment core PS1222-1. 96489 records from Colección Ornitológica del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 1150 records from Macrozooplankton concentrations estimated from MOCNESS tow samples, Continental Margin Western Antarctic Peninsula, GLOBEC. 856 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 187 records from (Table Ib) Planktic foraminifera abundances in the earliest Paleocene sample interval of DSDP Hole 74-528 on the Walvish Ridge, South Atlantic. 85 records from Unterbrucker Weiher. 59 records from Schulgelände SGD/Viersen. 58 records from Phytoplankton abundance in surface water during Akademik Vernadsky cruise AV24. 9 records from Abundance and biomass of phytoplankton in the Aral Sea. 10 records from (Table A) Abundance of species detected in mussel beds within hydrothermal fields on the Mid-Atlantic Ridge. 170 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 12 records from Occurrence of mammalia relicts at site Luttenberg. 102 records from Dinocyst assemblages of site HM52-43. 278 records from Planktic foraminifera abundance of Hole 39-354. 336 records from Planktic foraminifera abundance of Hole 42-375. 47 records from Planktic foraminifera abundance of Hole 72-515. 22 records from Planktic foraminifera abundance of Hole 94-609A. 99 records from Planktic foraminifera abundance of Hole 94-610E. 172 records from Range table from planktonic foraminifers in ODP Hole 141-863B. 31 records from Range table from planktonic foraminifers in ODP Hole 170-1042A. 525 records from Benthic foraminifera abundance of Hole 40-360. 87 records from Range table from benthic foraminifers in ODP Hole 182-1131A. 404 records from Range table from benthic foraminifers in ODP Hole 189-1171D. 171 records from Range table from benthic foraminifers in ODP Hole 198-1211B. 362 records from Range table from benthic foraminifers in ODP Hole 149-898B. 2476 records from Range table from benthic foraminifers in ODP Hole 154-929A. 398 records from Dinoflagellate abundance of Hole 81-555. 26 records from Dinoflagellate abundance of Hole 81-554. 14 records from Microfossil abundance of Hole 29-277. 24 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1171C. 192 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru. 1125 records from Benthic foraminifera of sediment core M25/4-KL13. 374 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_91MC. 80 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 2. 29 records from Range table from planktonic foraminifers in ODP Hole 173-1065A. 2 records from Dinoflagellate abundance of Hole 85-572C. 1 records from Pollen and spore abundance of Hole 42-379A. 195 records from Phytoplankton abundance in surface water in May 1997, Callao, Peru. 1769 records from Distribution of benthic foraminifera in DSDP Hole 24-238 in the Central Indian Ocean (Appendix A). 571 records from (Appendix A2) Relative abundances of benthic foraminifera and stable carbon isotope ratios of Nuttallides truempyi at the Paleocene-Eocene thermal maximum in ODP Hole 198-1210B in the central Pacific. 1224 records from Relative abundances of benthic foraminifera at the Cretaceous/Paleogene boundary in DSDP Hole 62-465A, Southern Hess Rise in the central North Pacific (Appendix A). 19 records from Auenwiesen und Trockenrasen. 70 records from Exotic terrestrial flatworms, Macquarie Island. 480819 records from KTP Ring Data. 52 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1018. 2 records from (Table 4) Differences in king penguin (Aptenodytes patagonicus) colony arrivals and departures based on age, Possession Island. 98229 records from British Lichen Society - BLS Lichen Database: Wales. 144 records from Taxonomy of the South American genus Pachypops Gill 1861 (Teleostei: Perciformes: Sciaenidae), with the description of a new species.. 156 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 1 records from Oppia glaucina. 10909 records from Irish Wetland Birds Survey (I-WeBS) 1994-2001.. 9383 records from tan-database. 164 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Arroyo Sauce Grande (Monte Hermoso). 35287 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 148 records from Abundance of birds in the Lena Delta Region. 9140 records from EDIT - ATBI in Gemer area (Slovakia). 661 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 290333 records from AMNH Mammal Collections. 3207 records from UAFMC Herps. 45 records from Pseudecheneis maurus, a new species of glyptosternine catfish (Teleostei: Sisoridae) from Central Vietnam.. 4203 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 313 records from Genera of the Asian Catfish Families Sisoridae and Erethistidae (Teleostei: Siluriformes).. 31 records from Descriptions of a new species and previously unknown males of Nesticus (Araneae: Nesticidae) from caves in Eastern North America, with comments on species rarity. 1 records from First record of Eggplant Mealybug, Coccidohystrix insolita (Hemiptera: Pseudococcidae), on Guam: Potentially a major pest. 801904 records from Queensland Museum provider for OZCAM. 686515 records from Lund Botanical Museum (LD). 569 records from (Appendix D) Benthic foraminifera extinction group species in DSDP Hole 94-608. 319 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD4. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Heliornithidae. 235 records from Pseudoscorpions of Ireland. 18 records from RSPB - Black grouse lek survey in Lothian and Borders, 2008 (RSPB). 13 records from Cresswell Associates - Wildlife Surveys in Southern Scotland 2007-2011. 31 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 55 records from A taxonomic revision of the Pheidole roosevelti-group (Hymenoptera: Formicidae) in Fiji.. 42 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Passeridae. 4 records from A new platygastrid wasp from Florida (Hymenoptera: Platygastridae).. 65 records from Revalidation and redescription of Pterocryptis anomala (Herre, 1933), a catfish (Teleostei: Siluridae) from southern China.. 4108 records from Anthomyiidae Study Group - Anthomyiidae records for Great Britain. 119 records from Redescription of Tetramorium forte Forel, 1904 (Insecta: Hymenoptera: Formicidae), a western Mediterranean ant species.. 2513 records from Carabidae of the Tatra Mts.. 41 records from (Table 3) Foraminiferal census data and derived sea surface temperatures in sediment core JM01-1199, southern Barents Sea. 15 records from NOTE SU ALCUNE SPECIE DEL GEN. EUPOLYBOTHRUS DELLA FAUNA DI GRECIA (Chilopoda, Lithobiomorpha). 1 records from Carabodes cephalotes. 152 records from Investigación y manejo para la conservación de tortugas amenazadas de los humedales llaneros. 10 records from Beitrag zur Kenntnis der Oribatiden Mitteleuropas (Neue Liacarus-Arten). 1932 records from (Table 6) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-852B. 6314 records from UWYMV Mammal Collection (Arctos). 264441 records from European Seabirds at Sea (ESAS) bird sightings from 1980 to 2003.. 336 records from (Table AT4) Planktonic foraminiferal stratigraphy of ODP Hole 182-1128C. 496 records from Macroinvertebrate abundance in montane tropical streams of varying land-use, Ecuador. 531 records from Ichthyofauna of the Kubo, Tochikura, and Ichinono river systems (Kitakami River drainage, northern Japan), with a comparison of predicted and surveyed species richness. 1311 records from (Table 3A) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572 and 85-572A. 4 records from Taxonomy of Afrotropical and West Palaearctic ants of the ponerine genus Hypoponera Santschi (Hymenoptera: Formicidae).. 1020718 records from Consortium of California Herbaria. 568 records from Coleccion Paleoinvertebrados CCT Mendoza - CONICET. 121542 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 13403 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 36974 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 17802 records from The Bat Conservation Trust - Colony Count Survey. 367092 records from HMAP-History pf Marine Animal Populations (CoML). 5730 records from Cercle des mycologues de Montréal Fungarium (CMMF). 36 records from New ants (Hymenoptera: Formicidae) from Micronesia.. 90 records from University of Amsterdam (NL) - Páramo Vegetation Research, paramo in the Sabana de Bogota area, Colombia. 5605 records from Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 27 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 15 records from Chenopodium. 915 records from Colección de Coleoptera (Tenebrionidae) del sureste de la Península Ibérica de la Universidad de Granada. 3065 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 10317 records from KUBI Ichthyology Tissue Collection. 68 records from RSPB - Bean geese on the Slamannan Plateau, Central Scotland between 1993 and 1995 (RSPB/SNH/Bean Geese Action Group). 17 records from Schutzgebiet Ochtersum. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 4472 records from MVZ Bird Observations (Arctos). 68 records from Streuobstwiese. 23 records from Ackerrain Plönhagen. 709 records from Upper Silesian Museum, Bird Collection. 1120 records from Dpto. de Zoologia y Antropologia Fisica, Universidad de Murcia. 402 records from Tag der Artenvielfalt in Heidelberg. 2 records from Neue Oribatiden (Acari) aus Deutschland III. Suctobelba carcharodon n. sp. und Suctobelba prominens n. sp.. 101 records from BIRDRACE nabu-rhein-main.de. 35 records from Scottish Natural Heritage - Information on capercaillie distribution collected during the âProductivity of breeding Capercaillie Tetrao urogallus at sites across their Scottish range 2011â monitoring project.. 70 records from Plasm bearing foraminifera counts from multinet SO119_MSN1283. 97 records from Total foraminifera counts from M35/1_MSN1061. 146 records from Total foraminifera counts of multinet PO200/6_MSN837. 563 records from Foraminifera abundance of Hole 74-526A. 15 records from (Table 1) Occurrence and abundance of late Early Cretaceous radiolarians at DSDP Hole 62-463. 63 records from Revision of the ant genus Myrmoteras in the Malay Archipelago (Hymenoptera, Formicidae).. 3762 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 1119094 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 2708 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1218A and 199-1219A sediments. 1752 records from Herbier National de Mauritanie (HNM). 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 544 records from Glasgow Museums BRC - The Changing Flora of Glasgow: Orchid Dataset. 97 records from Birdrace-Die_Bonnapartemöwen-Rhein-Sieg-Kreis. 167 records from Zielbach (Töll). 36 records from Plöwener Wald. 15 records from Bodentiere rund um die Schule. 6 records from Sächsische Schweiz (Pfaffenstein). 8 records from Eichendorf Weiher Schwalbach a.Ts.. 52 records from Aktion der Klasse H2 in Simmelsberg. 11 records from Balantiocheilos ambusticauda, a new and possibly extinct species of cyprinid fish from Indochina (Cypriniformes: Cyprinidae).. 1 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 5 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, >125 µm fraction. 92 records from Total foraminifera counts from multinet SO119_MSN1295. 91 records from Plasm bearing foraminifera counts from multinet M32/3_MSN957. 176 records from Total foraminifera counts of multinet M21/2_MSN656. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 112 records from BIRDRACE Gütersloher Gimpel. 99 records from VFD HH/SH "Pferdeweide Lemsahl". 109 records from Assemblage of living benthic foraminifera in sediment core GeoB3703-4. 194 records from Total foraminifera counts from multinet M32/3_MSN958. 63 records from Plasm bearing foraminifera counts of multinet SO117_MSN1245. 177 records from Donauinsel des BN bei Entau. 9445 records from Invertebrate specimens in the Wakayama Prefectural Museum of Natural History, Japan.. 267 records from Ostracoda abundance of Hole 95-613. 19 records from Nannofossil abundance of Hole 31-298. 11 records from Nannofossil abundance of Hole 11-101. 20691 records from Cladocera and Copepoda. 46 records from Antarctic Isopods. 1499 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 1534 records from Pontaurus. 1988 records from Texture description and distribution of components in ODP Hole 103-639D (Figure 2). 2676 records from Abundance of benthic infauna in surface sediments from the North Sea sampled with TYRO in 1986. 11843 records from Distribution of planktonic foraminifera in sediment core MD95-2040. 18473 records from Australian Antarctic Division Herbarium. 313949 records from United States National Plant Germplasm System Collection. 1902 records from Water Colours of Fungi by Fritz Wohlfarth at the Botanische Staatssammlung München. 16 records from (Table 5) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-841A. 177494 records from Primer censo de plantas leñosas de una Parcela Permanente de 25 hectáreas, ubicada en la Reserva Natural La Planada (Nariño, Colombia). 112 records from Plasm bearing foraminifera counts of multinet M21/2_MSN643. 14 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 25 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC09. 328 records from Abundance of calcareous dinoflagellates of sediment core GeoB1214-1. 5 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_818-16. 1 records from Microzooplankton abundance and biomass at station TT050_4-7. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-23-2. 16 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru. 71 records from Microzooplankton abundance measured on water bottle samples at station PS58/107-5. 12 records from Distribution of meiobenthos in sediment core M19_239-2 of the northeastern Atlantic (Table 1). 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 6 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from the Andean Cordillera of Perú with comments on relationships within the genus.. 45 records from (Table A.09) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (125-250 µm). 21 records from Table 1. Location, water depth, grain size distribution, organic carbon and carbonate contents of the investigated Arctic and Antarctic surface sediment samples. 3670 records from Royal Ontario Museum - Entomology (ROME). 59 records from Schriesheimer Steinbruch. 142 records from MfN - Fossil vertebrates I. 73 records from Planktic foraminifera abundance of Hole 2-11. 169 records from Abundance of planktic foraminifera at CTD station PS55/051. 7 records from Microplankton counts and carbon biomass at station TT012_5-CTD59. 656 records from ZFMK Sound Archive. 684 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 181-1119. 50 records from Leben in den Elbwiesen. 28 records from Smear slide analysis on sediment core GeoB4217-5. 25 records from Coccosphere-units of site GIK23414. 45 records from Nannofossil abundance of Hole 64-481A. 30 records from Nannofossil abundance of Hole 8-71. 24 records from Nannofossil abundance of Hole 11-106. 15 records from Diatom abundance measured on water bottle samples at station PS58/009-2. 14 records from Benthic macrofauna abundance of sediment core 12930-095. 201 records from Seawater carbonate chemistry and processes during experiments with coccolithophores (Emiliania huxleyi and Gephyrocapsa oceanica), 2000. 503 records from Dinoflagellate cysts from sediment core PS2138-1. 61 records from BIRDRACE Bergische Ornis. 3772 records from Fish (KIWE-PI). 4717 records from Weddell Sea macrozoobenthos EASIZ I. 638 records from MNA - Sezione di Genova - (Marine Biological Samples). 94 records from Collection Bryozoa - ZMB. 600 records from (Table 2) Percent distribution of calcareous nannofossils at ODP Hole 125-782A. 578 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE293. 1048 records from Biodiversidad y dinámica espacio-temporal del ictioplancton de dos sistemas lagunares de la Reserva de la Biósfera de Sian Ka'an. 1877 records from Odonata de la huasteca potosina (insecta). 56 records from Ostracod species in Oligocene sediments of core CRP-2A. 12 records from Nannofossil abundance of Hole 78-542. 5 records from Nannofossil abundance of Hole 84-569. 5 records from Nannofossil abundance of Hole 74-529. 14 records from Nannofossil abundance of Hole 85-573. 20 records from Nannofossil abundance of Hole 24-232. 58 records from Nannofossil abundance in sediment core PS1295-5. 13 records from Benthic macrofauna abundance of sediment core 13200-008. 92 records from Planktic foraminifera counts of sediment core V19-204. 1044 records from (Table 4a) Calcareous nannofossil distribution on ODP Hole 117-721A. 1298 records from Colección de Aves y Mamíferos del Valle de Cuatrociénegas, Coah., México (UANL). 43199 records from FKSE-Herbarium specimens of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 746 records from RMT Trawl catch from the 1986/87 V7 AAMBER voyage. 1340 records from (Figure 2) Distribution of dinoflagellate cysts in the mid-Cretaceous of ODP Hole 101-627B. 111 records from (Table 8) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-662A. 52 records from (Table 11) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-665A. 299 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE272. 126 records from (Table 1) Range chart of calcareous nannofossils in ODP Hole 122-761B. 110 records from (Table 3) Meiofauna abundance in surface sediments of Cape Lookout. 2357 records from Foraminifera abundance of Hole 17-167. 52 records from (Table 2) Abundance of total planktonic foraminifera and Neogloboquadrina pachyderma in sediment core KNO5103-0029GGC. 210 records from Pliocene/Pleistocene benthic foraminiferal abundances from ODP Hole 167-1012B. 256 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 1306 records from Flora genérica de las gramíneas del estado de Tlaxcala. 1756 records from Flora de la reserva de la biósfera de los Pantanos de Centla, en el estado de Tabasco, México. 7208 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 1202 records from (Table 18) Ranges of benthic foraminifers through the Neogene in DSDP Hole 23-219. 6557 records from (Table 5) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-707A. 45 records from Collection Arachnologie fossil - SMF. 32642 records from mammals. 2095 records from The SERTC Invertebrate Database: Invertebrates of the southeastern United States. 19614 records from Mammal specimens. 6957 records from Botanical Museum, Copenhagen, the Lichen Herbarium. 10607 records from Desmidiaceae Engels. 976457 records from EURISCO, The European Genetic Resources Search Catalogue. 5346 records from Araneidae specimen database of Osaka Museum of Natural History. 30625 records from Kochi Prefectural Makino Botanical Garden. 170 records from Distribution of planktic foraminifera of sediment core GIK23411-5. 1194 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V29-29. 15312 records from UCM Mammal Collection (Arctos). 425 records from Moss sampling in the Windmill Islands and the Vestfold Hills. 112 records from Landschaftsschutzgebiet Hexenberg (Erftstadt-Erp). 952 records from Foraminifera abundance of Hole 17-171. 8933 records from Inventario de la biodiversidad de vertebrados terrestres de los Chimalapas, Oaxaca. 236 records from Los peces del área oaxaqueña de la Reserva de la Biosfera Tehuacán-Cuicatlán. 688 records from Banco de información sobre características tecnológicas de maderas mexicanas. 21296 records from Nearctic Spider Database. 1405 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AVES. 591 records from Alan Wormington Collection. 2483 records from Bacteria collection of National Institute of Public Health, Poland. 1389 records from (Table T5) Planktonic foraminifera abundance of ODP Hole 170-1043A sediments. 906 records from Percentages of planktonic foraminifera species in sediment core V15-168. 139 records from Planktic foraminifera assemblage in sediment core GIK23071-3. 343 records from Foraminifera abundance of sediment core IN68-23. 808 records from (Table 2) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 113-690C on Maud Rise, Weddell Sea. 2628 records from GEO Hauptveranstaltung Tirol (Innsbruck). 670 records from Pilstingermoos. 35 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 105 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB06 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 10 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-MNB5. 15 records from Occurrence of mammalia relicts at site le gisemnet de Fongabon. 37 records from Occurrence of mammalia relicts at site Fohlenhaus-Höhlen. 6 records from Occurrence of mammalia relicts at site Mitoc Malul Galben. 7 records from Radiolaria assemblage in sediment core GIK23424-3. 336 records from Planktic foraminifera abundance of Hole 6-47B. 145 records from privater Garten. 608 records from Distribution of planktic foraminifera in sediment core GIK16396-1. 85 records from Schulgelände IGS Kaufungen. 124 records from Umgebung der Elsa-Brändström-Schule (Krückaupark). 170 records from Schlattstaller Tal (Lenningen). 219 records from Prophetensee Quickborn. 124 records from Occurrence of mammalia relicts at site Euerwanger Bühl. 16 records from Occurrence of mammalia relicts at site Dorog. 376 records from Planktic foraminifera abundance of Hole 22-216. 290 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 182 records from Benthic foraminifera and algae abundance of Hole 81-554. 1045806 records from Belgian IFBL Flora Checklists (1939-1971). 405 records from Freiburger Netzwerk Artenvielfalt. 45 records from NSG Dellwiger Wald, Dortmund. 44 records from Flora und Fauna in unserer Kita. 1236 records from Coleoptera of Biebrza National Park. 13267 records from CUMV Amphibian Collection (Arctos). 135 records from (Table T3) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049C. 3038 records from Museu Paraense Emilio Goeldi - Lepidoptera Collection. 8 records from Cirrhigaleus australis n. sp., a new Mandarin dogfish (Squaliformes: Squalidae) from the south-west Pacific.. 5 records from Cnesterodon holopteros (Cyprinodontiformes: Poeciliidae: Poeciliinae), a new species from the Republic of Uruguay.. 1582 records from Highland Biological Recording Group - HBRG Badger dataset. 779 records from Guadeloupe_Ananas. 172345 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine) data for Great Britain and Ireland. 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 7 records from Calvia explanata sp. n. (Coleoptera: Coccinellidae: Coccinellinae) from the Indian Subcontinent. 2476 records from EcoRecord - Bug (Hemiptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 9526 records from UK Cetacean Strandings Investigation Programme - Stranded cetacean data from Great Britain collected from 01/01/89 through to 31/03/10. 118 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB07 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 42 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500. 84 records from Occurrence of mammalia relicts at site Sütto_6. 2 records from Planktic foraminifera abundance of Hole 39-358. 85 records from Planktic foraminifera abundance of Hole 28-264A. 691 records from Foraminifera abundance of Hole 24-236. 369 records from Planktic foraminifera abundance of Hole 24-238. 2 records from Range table from planktonic foraminifers in ODP Hole 159-962C. 4 records from Evidence for the continued presence in New Zealand of Homotrysis macleayi (Borchmann, 1909) (Coleoptera: Tenebrionidae: Alleculinae). 295 records from Range table from planktonic foraminifers in ODP Hole 182-1130B. 127 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 13 records from Range table from benthic foraminifers in ODP Hole 194-1192A. 34 records from Nannofossil abundance of Hole 41-366A. 3 records from Diatom abundance of Hole 60-453. 271 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1168A. 96 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2039. 32312 records from Collection Aves (spirit preserved) SMF. 56214 records from Herpetology Collection. 1 records from Abundance of benthos infauna at station GIK23040-1. 17450 records from The Scottish Ornithologists' Club - Fife breeding bird tetrad atlas 1991-99. 27072 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 1445 records from (Table T4) Planktonic foraminiferal stratigraphy of ODP Hole 173-1069A sediments. 131 records from A contribution to the study of the Lower Volga center of scarab beetle diversity in Russia: checklist of the tribe Aphodiini (Coleoptera, Scarabaeidae) of Dosang environs. 427 records from Planktic foraminifera abundance of Hole 76-533A. 282 records from Foraminifera abundance of Hole 48-403. 94 records from Planktic foraminifera abundance of Hole 32-310. 3147 records from Range table from planktonic foraminifers in ODP Hole 159-959B. 44 records from Royal Horticultural Society - Pittosporum sucker (Trioza vitreoradiata) records acquired by the Royal Horticultural Society. 5 records from Benthic foraminifera abundance of Hole 42-371. 91 records from Range table from benthic foraminifers in ODP Hole 188-1165B. 8 records from Range table from benthic foraminifers in ODP Hole 188-1165C. 60 records from Range table from benthic foraminifers in ODP Hole 139-858C. 226 records from Range table from benthic foraminifers in ODP Hole 182-1130A. 5 records from Microfossil abundance of Hole 50-416A. 10792 records from Fungi specimen detabase of Kanagawa Prefectural Museum of Natural History. 19610 records from Colección del Departamento de Biología Animal (Zoología) de la Universidad de La Laguna. 352 records from Universidad de Málaga: MGC-Lichen. 13230 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Conidae. 278 records from A review of the species in the Apogon fasciatus group with a description of a new species of cardinalfish from the Indo-West Pacific (Perciformes: Apogonidae).. 5363 records from Colección Ornitológica de la Universidad del Valle. 60 records from crocodylus. 2046 records from (Table T3) Benthic foraminfera stratigraphy of ODP Hole 199-1221C sediments. 10567 records from Coleoptera collection of National Museum of Nature and Science. 11 records from (Table T6) Relative abundance of Cretaceous plant microfossil taxa of ODP Site 188-1166. 593 records from Amphibians and reptiles of Ireland. 391760 records from The Flora of County Wexford. 86 records from Alter Kreidebruch Saßnitz/Rügen. 5 records from Feuchtwiese. 104 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Motacillidae. 2324 records from Eriophyoid Mites of Poland. 18077 records from University of Manitoba Herbarium (WIN) - Vascular Plant Collection. 52 records from (Table 2) Sediment constituents and quartz in the sand-sized fraction, West Florida slope and Eastern Mississippi Fan, during USGS R/V Gyre cruises G80-6A and G81-8. 33 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 2467 records from Yorkshire Naturalists' Union Marine and Coastal Section - Yorkshire Naturalists Union Marine and Coastal Section Records. 1 records from Arthropoden aus südostalpinen Höhlen.. 25017 records from Flea (Siphonaptera) Recording Scheme - Flea (Siphonaptera) Distributions in Britain and Ireland: pre 1975, 1975 onwards. 7 records from On the centipedes (Chilopoda) of the Republic of Macedonia. 34 records from Orthoptera - SMNG. 1 records from Nothrus gibbus. 29 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 11004 records from Dataset of Phenology of flora of mediterranean high-mountains meadows (Sierra Nevada). 3 records from Revision der Ceratozetidae, 3. Ceratozetes laticuspidatus n. sp. (Arach., Acari, Oribatei). 51 records from Towards the conservation of parasitoid wasp species in Canada: Preliminary assessment of Microgastrinae (Hymenoptera: Braconidae). 10 records from Inventarios de Murciélagos Pauto M, La Primavera, Yopal, Casanare. 59534 records from Zoology (Museum of Evolution - Uppsala). 6541 records from Likona Invertebrates. 55 records from (Table 3) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840B. 1 records from On the morphology, biometry and biogeography of Lamtopyxis callistoma ( Amoebozoa : Arcellinida ). 76 records from BIRDRACE Nachtigallen. 5263 records from Colección Herpetológica (anfibios) de la Universidad Industrial de Santander. 52 records from Université Pédagogique Nationale de Kinshasa (UPN) - Données botaniques (2011)- Projet CABIN. 1453 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales de afloramiento rocoso del Parque Nacional Natural El Tuparro. 22683 records from Museu Paraense Emilio Goeldi - Araneae Collection. 115 records from (Table 4) Relative abundances of benthic foraminifera in ODP Hole 128-799B. 32450 records from Naturalis National Natural History Museum (NL) – Invertebrate specimens from marine expeditions. 46664 records from The Scottish Ornithologists' Club - Fife non-breeding bird 5km atlas 1991-99. 27988 records from Argyll Bird Club - Bird records for Argyll for the years 2002 and 2003. 28385 records from Plan de vertebrados de la Patagonia. 2922 records from National Lesser Horseshoe Bat Database. 8332 records from Joint Nature Conservation Committee - Scotland Otter Survey Database. 10 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 218 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 2. 6083 records from Biological Records Centre - Sepsidae (Diptera) records from Britain and Ireland to 1985. 2475 records from HSU Wildlife Eggs and Nests. 103 records from Mammalogie ZMK. 8326 records from Derbyshire Biological Records Centre - Derbyshire Invasive Vascular Plants (INNS) 1900 - 2011. 1369 records from Chromista Collection of the Seto Marine Biological Laboratory, Kyoto University. 57928 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 205653 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 128 records from Birdrace-Brut-Wetteraukreis. 11 records from Pollen profile from sediment core AV14_K2-4. 8 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XIX/3 (ANDEEP I). 13325 records from Herbier du Bénin. 3 records from A revision of the Neotropical spider genus Ancylometes Bertkau (Araneae: Pisauridae). 2 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 138 records from (Table 1) Late Pleistocene planktonic foraminifera of Hole 302-M0004C. 7356 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Moss and Liverwort Observation Records. Pre-2010 for Cumbria. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 8 records from Mit allen Sinnen durch den Wald / Schmücke (ev. Kita Heldrungen). 33 records from Schüler erforschen die Helme-Aue. 18 records from Assemblage of living benthic foraminifera in sediment core CD145_55808#3, >150 µm. 82 records from Total foraminifera counts of multinet FCA97C_MSN1346. 68 records from Total foraminifera counts of multinet M21/4_MSN701. 159 records from Total foraminifera counts of multinet M36/6_MSN1194. 54 records from Plasm bearing foraminifera counts of multinet M21/2_MSN629. 77 records from Total foraminifera counts of multinet PO231/3_MSN1330. 77 records from Foraminifera species abundances from tow TT011_9-MOC69. 12 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/091-3. 58 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/570-14. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 209 records from (Appendix A) Palynofacies absoulte abundances of DSDP Hole 38-338. 62 records from Amtsrain Apolda-Zottelstedt. 58 records from VFD-H. Heidenrod: Mähweide im Wasserschutzgebiet. 18 records from GEO-Tag der Artenvielfalt der Klasse 7c am Gymnasium Allee im Wohlers Park. 587 records from (Table 2) Raw counts of planktonic foraminiferal species and varieties from the sediment surface samples from the South China Sea. 149 records from Total foraminifera counts of multinet PO247/2_MSN1372. 85 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core GIK23059-2. 3 records from Sarcodine counts and carbon biomass at station TT007_12-CTD145. 938 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-175-1. 13 records from Phytoplankton abundance at station Casma_2003-03-27_2, Casma, Peru. 70 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 44 records from (Table F3) Occurrence of some well known benthonic foraminiferal species in samples from DSDP Site 6-49. 1 records from Wirtschaftsgrünland, Intensiv genutze Wiese. 90 records from Relative abundance of coccosphere-units of site GIK23259. 30 records from Nannofossil abundance of Hole 94-608. 9 records from Diatom abundance measured on water bottle samples at station PS58/038-3. 4 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB01 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 8 records from Little known Orphninae (Coleoptera, Scarabaeidae) collected by the Madagascan expeditions of the California Academy of Sciences. 642 records from Planktic foraminifera counts of sediment core V22-196. 753 records from Estación Experimental de Zonas Áridas (CSIC) EEZA-Mamif. 37 records from Palynological analysis of sediment core GeoB3910-2. 36 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, >125 µm fraction. 9 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, >150 µm. 23 records from Plasm bearing foraminifera counts from multinet M32/3_MSN958. 27 records from Total foraminifera counts of trap L3_92_45. 74 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core GIK23059-2. 52 records from (Table T8) Occurrence of Neogloboquadrina pachyderma in ODP Hole 178-1098C. 14 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/090-2. 133 records from Planktic foraminifera counts at CTD station PS55/079-1. 3 records from Microzooplankton abundance and biomass at station TT054_21-15. 1 records from Microzooplankton abundance and biomass at station TT054_24-22. 13 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Tytonidae. 10 records from Phytoplankton abundance at station Rigel_6_2005-02 in Febraury 2005, Chipana, Chile. 17 records from Phytoplankton abundance at station Sechin_2003-10-22_2, Casma, Peru. 42920 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 8 records from Distribution of meiobenthos in sediment core M19_197-2 of the northeastern Atlantic (Table 1). 75 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/356-1. 1278 records from (Appendix 2-6) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 58-445 in the western Pacific Ocean. 719 records from (Appendix A) Absolute abundances of planktonic foraminifera in Quaternary sediments of ODP Hole 174-1073A from the New Jersey margin, NW Atlantic Ocean. 24 records from Counts (2) of calcareous dinocysts along profile Stevns-Klint. 9 records from Microzooplankton abundance and biomass at station TT043_29-1. 11 records from Microzooplankton abundance and biomass at station TT045_13-10. 17 records from Phytoplankton abundance in surface water in 1996, Ancon, Peru. 103 records from Distribution of planktonic foraminifera of sediment core SH1972_10. 49 records from Heavy metals in abdominal parts of Pagurus bernhardus during VALDIVIA cruise VA44. 110 records from Artenvielfalt und Kulturlandschaft. 18166 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 21 records from Nannofossil abundance of Hole 6-55. 3 records from Nannofossil abundance of Hole 6-57B. 20 records from Nannofossil abundance of Hole 7-63A. 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/048-3. 18 records from Meiofauna abundance in sediment core 13368-015. 27 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI229. 1178 records from Birds (NMNO-BI). 478 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE278. 1470 records from EDIT - ATBI in Spreewald (Germany). 103 records from Pollen analysis of Site 175-1075 (part 1). 1 records from Zetes semirufus. 11333 records from Colección de referencia de vectores de Leishmania spp (causante de Leshmaniasis cutánea localizada) de la Península de Yucatán y un estudio preliminar en un área endémica de Quintana Roo. UADY_SNIB. 1 records from Collection Quaternary Small Mammals IQW. 37 records from Pollen profile from Arrington Marsh. 1312 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 54 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2247-1. 20 records from Abundance of radiolaria at station LV28-4-1. 27 records from (Table F3) Occurrence of some well known benthonic foraminiferal species in samples from DSDP Site 6-50. 54223 records from Fish Specimens. 185 records from Abundance of coccosphere-units of site GIK23414. 2 records from Nannofossil abundance of Hole 3-21A. 18 records from Nannofossil abundance of Hole 58-442A. 4 records from Range table from nannofossils in ODP Hole 139-857A. 13 records from Composition of the coarse silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 21 records from Meiofauna abundance in sediment core 54301-010. 53 records from Planktic foraminifera counts of sediment core ELT48.027-PC. 3012 records from GSPB Prokarya Catalogue. 88 records from Ober-Olmer Wald 09. 440 records from Antarctic and Subantarctic Asteroid zoogeography. 781 records from (Table 2) Benthic foraminiferal assemblage in the early Pleistocene interval of ODP Site 162-984. 24 records from (Table 4) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-681A. 189 records from (Table 16) Distribution of ostracode species in Core PS51/080-13. 2713 records from Relative abundances of planktonic foraminifera in ODP Site 121-758 (Table 1). 3139 records from (Appendix A) Agglutinated foraminifers in ODP Hole 123-765C. 160 records from (Table 5) Distribution of Pleistocene to late Oligocene nannofossils in ODP Hole 108-659A. 98 records from (Table 10) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-664A. 936 records from (Figure 3) Distribution chart of dinoflagellate cysts of Cretaceous age from ODP Hole 103-638B. 1272 records from (Table 2) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-706A. 500 records from Anfibios y reptiles del municipio de Cuetzalan del Progreso, Puebla. 735 records from Diversidad de coleópteros scarabaeoidea del estado de Puebla (I). 1834 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Mariposas. 2106 records from (Table 17) Ranges of benthic foraminifers through the late Neogene in ODP Hole 115-713A. 4580 records from BCCM/IHEM - Biomedical Fungi and Yeasts Collection. 292 records from Atlantic Forestry Centre Insect Reference Collection. 180013 records from Arctic Ocean Diversity. 241 records from CNIN/Tipos Odonata. 1534 records from PonTaurus collection. 272 records from Coarse fraction analysis of sediment core PS1730-2. 1098 records from Percentages of planktonic foraminifera species in sediment core V25-60. 918 records from Planktic foraminifera distribution of sediment core KET80-19. 47 records from Antarctic Euphausiacea occurrence data from Norwegian Antarctic Research Expedition 1979. 61 records from Steinbruch Pluwig. 25942 records from Institut Mediterrani d'Estudis Avançats: IMEDEA-PALEOVERT. 1010 records from Distribución y algunos aspectos ecológicos de hongos hidnoides estipitados de México. 251 records from Evaluación del estatus de los géneros Pereskiopsis y Pereskia (Cactaceae) en los Apéndices de la CITES. 1464 records from Inventario ficoflorístico de las comunidades arrecifales del Parque Nacional Bahías de Huatulco, Oaxaca. 76025 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 1505 records from Inventario de los mamíferos de las reservas de la biósfera Mapimí, La Michilía, El Cielo y Calakmul. 32575 records from Tartu University, palaeontology collections. 731 records from Danish Grasshoppers (Orthoptera). 251 records from GBIF-D Protozoa data collection. 1794 records from Elephant Seal Sightings, Heard Island. 5311 records from Gulf of Maine Bottom Trawl Survey Data (NEFSC,NMFS,NOAA)(USOBIS). 34865 records from Hexacoral Database. 5000 records from Lichen Collection of National Museum of Nature and Science. 2940 records from The Erysiphales Collection at the University Halle-Wittenberg. 5231 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Collection of Martin Schnittler. 15647 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 6 records from Sediment properties of core CD86_09_PC. 1464 records from CNIN/Tipos Coleoptera. 19 records from Microplankton data off Chipana Bay, 2006, Chile. 1441 records from (Table 1) Count data of organic-walled dinoflagellate cysts in surface sediment samples from the Benguela System. 1 records from Occurrence of mammalia relicts at site Warsaw. 10 records from Occurrence of mammalia relicts at site Adler Cave xx. 16 records from Abundance of radiolaria at station LV28-3-3. 3379 records from (Table 14A) Occurrences of planktonic foraminifers in DSDP Hole 90-592, samples 592-1-CC through 592-29-CC. 205 records from Planktic foraminifera abundance of Hole 29-284A. 2421 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 5918 records from Catálogo y recopilación de datos científicos de los lepidópteros nocturnos de México, pertenecientes a cinco familias. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 44298 records from Ichthyology, Kagoshima University Museum. 37963 records from Zoological collections of the University of Tartu. 1760 records from (Table 9) Planktonic foraminifera of late Quaternary sediments in DSDP Hole 41-368. 127 records from (Appendix E) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758B. 17369 records from MfN - Auchenorrhyncha Collection. 55189 records from UWBM Mammalogy Collection. 24958 records from CABI Bioscience Genetic Resource Collection. 156948 records from NBI. 49406 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1985) (AfrOBIS). 4641 records from Lepidopterists Society Season Summaries 1973-1997. 205 records from Japan Collection of Microorganisms(Basidio). 126 records from Kelp rafts in the Southern Ocean. 3634 records from Herpetological collection of National Museum of Nature and Science. 138 records from Visual Plants (144.41.33.158) - Herbarium specimen from "BIEL", Germany. 29876 records from European Moth Nights. 655171 records from Bugbase, Lepidopterological Society. 5 records from Analyses of the recent components of sediment core PS1422-1. 530 records from Nemertina World Checklist. 60 records from Schulumgebung Grüterschule, Rheine. 226 records from Himmelmoor. 12 records from Microplankton abundance at bottle station SEPT-1999-K1. 21 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JANUARY-1995-D4. 5 records from Occurrence of mammalia relicts at site Victoria Cave. 122 records from Occurrence of mammalia relicts at site Hunas. 126 records from Occurrence of mammalia relicts at site Gare de Couze-Serie 2. 1028827 records from SEAMAP - marine mammals, birds and turtles. 1080 records from Distribution of major planktic foraminifer at Site 177-1088. 1 records from Range table from planktonic foraminifers in ODP Hole 185-1149B. 20 records from (Table 2c) Nannofossil distribution chart of ODP Hole 122-762C. 20 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station MARCH-1995-D2. 18 records from Range table from planktonic foraminifers in ODP Hole 180-1109A. 2443 records from Distribution of benthic foraminifera of sediment core PS1388-3. 2453470 records from Finnish Entomological Database: Lepidoptera. 1471 records from EcoRecord - Bryophyte records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 634530 records from NSW herbarium collection. 690 records from DSMZ Collection of Plant Viruses. 556 records from Distribution of planktic foraminifers of sediment core D117. 31 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200800. 39 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 141-861C. 12 records from (Table 1) Abundance and biomass of diatom algae, dinofiagellates, green algae, and flagellates and their percentages in total phytoplankton abundance and biomass in the Obskaya Guba and adjacent Kara Sea in the latest September 2007. 1039 records from inta-herbario-bab. 370 records from Benthic foraminifera counts of sediment core PS1244-2 (GIK23244-2). 9 records from Trap data GBN3, 3921 m. 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-065. 4 records from Description of lithologic section units of IODP Hole 325-M0052B. 14219 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 189 records from (Table A.09) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (125-250 µm). 12 records from Microplankton abundance at bottle station SEPT-1999-K9. 68 records from Occurrence of mammalia relicts at site Schweizerbild. 4 records from Planktic foraminifera abundance of Hole 54-422. 175 records from Range table from planktonic foraminifers in ODP Hole 155-931A. 4021 records from (Figure 7) Distribution of benthic foraminifers in the Oligocene to upper Miocene DSDP of Hole 71-513A. 117 records from Benthic foraminifera and algae abundance of Hole 81-552. 216 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 85 records from Range table from benthic foraminifers in ODP Hole 154-929B. 3864 records from Mammal specimen database of Kanagawa Prefectural Museum of Natural History. 893 records from (Table T1) Neogene dynoflagellate cyst occurrence in ODP Hole 186-1151A sediments. 1 records from Chilopoden und Diplopoden aus Jugoslavischen Höhlen. 319 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Pandionidae. 422 records from (Table T1) Planktonic and benthic foraminifer abundance of ODP Hole 183-1138A. 117 records from (Table T5) Calcareous nannofossil stratigraphy of ODP Hole 198-1209C. 95 records from Isotope tracer experiment: nematode isotope ratio. 637 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales de Bahía Málaga, municipio de Buenaventura, Valle del Cauca. 4 records from Pollen analysis of sediment profile HAE10 from Haemelsee. 90 records from Quaternary radiolarians from offshore eastern New Zealand, ODP Leg 181, Site 1123, relative abundances. 25 records from Foraminifera abundance of Hole 55-430A. 53 records from Planktic foraminifera abundance of Hole 29-281A. 237 records from Planktic foraminifera abundance of Hole 32-305. 37 records from Planktic foraminifera abundance of Hole 27-260. 26 records from Planktic foraminifera abundance of Hole 84-567. 5 records from Range table from planktonic foraminifers in ODP Hole 151-912A. 1142 records from Range table from planktonic foraminifers in ODP Hole 154-925A. 990 records from (Tab. 13) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 32-306, Shatsky Rise southeast of Japan. 45068 records from Colección Nacional de Herpetología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 31 records from Dinoflagellate abundance of Hole 81-552A. 92 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 776 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_98MC. 301 records from (Appendix 4, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 10 records from Oberservation of birds at station PS14/149 along 49° West. 11098 records from Herbario de Universidad de Murcia: MUB. 1 records from Ueber Chilopoden aus westbalkanischen Hoehlen. 1423 records from Inventaire National du Patrimoine Naturel : CBN du Massif Central. 5722 records from Insect Arthropods (KIDR-IN). 23408 records from Herbarium specimens of the Muséum d'Histoire Naturelle of Aix-en-Provence (AIX). 36657 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 255559 records from Northern Ireland Environment Agency - EHS Species Datasets. 136 records from Planktic foraminifera abundance of Hole 63-468. 57 records from Range table from planktonic foraminifers in ODP Hole 152-915A. 122 records from Range table from planktonic foraminifers in ODP Hole 170-1041A. 5 records from Range table from planktonic foraminifers in ODP Hole 171-1049C. 251 records from Benthic foraminifera abundance of Hole 80-549A. 275 records from Range table from benthic foraminifers in ODP Hole 198-1209A. 72 records from Range table from benthic foraminifers in ODP Hole 198-1213A. 238 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-967A. 3638 records from (Table 3) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-502A from the Caribbean Sea. 24 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 39 records from Benthic meiofauna abundance in surface sediment during cruise CD86. 5759 records from EcoRecord - Mammal records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 1078 records from Fishes of the Congo River 2010 Expedition. 35 records from Neoniphon pencei, a new species of holocentrid (Teleostei: Beryciformes) from Rarotonga, Cook Islands. 162150 records from Ditsong Museum. 23 records from New species of the plesiomorphic genus Nixonia Masner (Hymenoptera: Platygastroidea, Platygastridae) from South Africa.. 20891 records from Biological Records Centre - Brachycera (Diptera) records from Britain and Ireland to 1990. 5468 records from Orchid Herbarium Collection. 87143 records from Sheffield Bird Study Group - Sheffield Bird Study Group (Yorkshire records). 13631 records from Beetles (LSM). 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 3 records from Note su alcune specie di chilopodi della regione palestinese. 5368 records from Dutch Mammal Society (NL) - Mammal observations extracted from historic reports. 15879 records from HAMAB - Herbário Amapaense. 289 records from (Appendix B) Nannofossil abundance in ODP Hole 165-998A sediments. 4 records from On the Chilopoda from Turkey. 264 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - RISC Heteroptera Non-Native Species Records. 31 records from Herbier Husnot, Hepatica Galliae. 31 records from (Table 4) Abundance of under-ice amphipods on flat ice and ice ridges sampled during the 2005 Hidden Ocean expedition. 2 records from A new species of the genus Xysticus C. L. Koch from Turkey (Araneae: Thomisidae). 2 records from Ueber Chilopoden aus westbalkanischen Hoehlen. 1276 records from Escarabajos coprófagos (Scarabaeidae: Scarabaeinae) del eje cafetero Colombiano. 4498 records from Colección Herbario Universidad Católica de Oriente. 18501 records from Biological Records Centre - Lacewings and allied insects records from Britain and Ireland to 1999. 76 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 97 records from DMNH Eggs. 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 99300 records from Landesmuseum Kärnten. 661414 records from Phanerogamic Botanical Collections (S). 28383 records from Notes from the Mycology Herbarium, Oslo (O). 75791 records from SAIAB. 8 records from New species of the catfish genus Trichomycterus (Siluriformes, Trichomycteridae) from the headwaters of the rio São Francisco basin, Brazil.. 65486 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 1287 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 6 records from Arthropoden aus südostalpinen Höhlen. 439 records from Museu Paraense Emilio Goeldi - Scorpiones Collection. 8 records from (Table 1) Distribution of benthic foraminifera in GIK_Plankton-B sample. 149 records from (Appendix C) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-967A. 631043 records from iNaturalist research-grade observations. 30000 records from Birds collection of Yamashina Institute for Ornithology. 461 records from nazza. 96 records from (Table T4) Biogenic and mineral composition of sediments cored in Hamburg-Langenhorn. 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 3 records from Collection Crustacea - ZSRO. 32109 records from Herbier de Nouvelle-Calédonie. 121 records from (Table 2) Relative contents of planktonic foraminifera in bottom sediments from the Ashadze-1 Hydrothermal Field. 26 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 81 records from Stadtpark Schmölln. 42 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 67 records from Plasm bearing foraminifera counts from M35/1_MSN1054. 64 records from Plasm bearing foraminifera counts from M35/1_MSN1063. 46 records from Plasm bearing foraminifera counts of multinet M27/2_MSN884. 53 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/509-16. 8 records from Microplankton counts and carbon biomass at station TT008_5-CTD25. 109 records from ZFMK AMIBIO. 4 records from Distribution of meiobenthos in sediment core M19_223-2 of the northeastern Atlantic (Table 1). 3219 records from (Appendix Table 2) Absolute abundances of benthic foraminifers in DSDP Site 94-610. 56 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 119-744. 33 records from (Figure 2b) Distribution of age indicator species of planktic foraminifera at Site 62-463. 142 records from Planktic foraminifera counts of sediment core V20-175. 1 records from Miriapodi di alcune grotte della Campania. 151 records from Biosphärenreservat Mittelelbe. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 301 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 40530 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 43298 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 164 records from Taxonomy of the catfish genus Pseudoplatystoma Bleeker (Siluriformes: Pimelodidae) with recognition of eight species.. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 23 records from Alter Nördlicher Friedhof (München). 20 records from Motzener Tonsee. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 40 records from Flächennaturdenkmal Grubditz. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 54 records from Biotope im Schulumfeld. 334 records from (Appendix 2) Stratigraphic distribution of key and potential stratigraphic calcareous nannofossil markers in the upper Campanian-Maastrichtian of ODP Hole 122-762C. 141 records from Assemblage of living benthic foraminifera in sediment core GeoB3702-2. 108 records from Total foraminifera counts of multinet M21/2_MSN629. 45 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1385. 57 records from Upper Aptian Serre Chaitieu (Niveau Fallot) G. ferreolensis and G. blowi per gram sediment, SE France. 20 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5132-3. 102 records from Foraminifera species abundances from tow TT011_11-MOC72. 125 records from Planktic foraminifera counts at CTD station PS55/082-1. 111 records from Abundance of planktic foraminifera at CTD station PS55/037. 32 records from Biological data measured on water bottle sampels at station AT_II-119/5_35-4. 8 records from Microzooplankton abundance and biomass at station TT045_29-1. 252 records from (Table T11) Calcareous nannofossil stratigraphy of ODP Hole 198-1212B. 713 records from (Figure 6) Total organic carbon content and counted dinoflagellate cysts of sediment core GeoB10706-3. 39 records from ECOCEAN MantaMatcher. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 217 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 65 records from LSG "Großes Bruch". 249 records from BIRDRACE DEVK-Deutschlands Enthusiastischste Vogel Kucker. 138 records from BIRDRACE Arkonauten. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Akassine*. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 29 records from Waldwiese. 54 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >125 µm. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, >125 µm fraction. 7331 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 142 records from Assemblage of living benthic foraminifera in sediment core GeoB4904-7. 10 records from Plasm bearing foraminifera counts from multinet M31/2_MSN894. 135 records from Total foraminifera counts of multinet M11/1_MSN522. 3 records from A new species of whiptail stingray of the genus Dasyatis Rafinesque, 1810 from the Southwestern Atlantic Ocean (Chondrichthyes: Myliobatiformes: Dasyatidae).. 12 records from Succession of benthic hard-bottom communities abundance at Liliguapi in 2011. 130 records from Plasm bearing foraminifera counts of multinet M21/1_MSN607. 42788 records from Merseyside BioBank - North Merseyside Insects (unverified). 11 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5117-1. 195 records from (Table T2) Concentrations and accumulation rates of Globorotalia menardii at ODP Hole 175-1087A. 9 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/012-4. 144 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 78 records from Phytoplankton counted on two fractions of surface sediment samples from Meteor stations M35003-4 to M35010-3. 5 records from Microzooplankton abundance and biomass at station TT050_7-9. 8 records from Phytoplankton abundance at station Casma_2003-01-07_2, Casma, Peru. 16 records from Phytoplankton abundance at station Casma_2003-03-27_1, Casma, Peru. 67 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 2 records from DNA barcoding reveals a new record of Potamogeton distinctus (Potamogetonaceae) and its natural hybrids, P. distinctus × P. nodosus and P. distinctus × P. wrightii (P. ×malainoides) from Myanmar. 53 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1a. 66 records from Nanoplankton abundance at station GeoB2012-5. 9 records from Nannofossil abundance of Hole 15-150. 11 records from Nannofossil abundance of Hole 15-153. 2 records from Nannofossil abundance of Hole 20-202. 420 records from Relative abundance of ostracods in sediment core St09. 2 records from Nannofossil abundance of Hole 25-249. 11 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 21 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD56. 1698 records from MNA Italica 2004_Rauschert dredge_Ross_sea_Mollusca_lgp. 12 records from Phytoplankton abundance at station Casma_2003-04-14_1, Casma, Peru. 15 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2445-2. 37 records from (Table 4) Carbon flux, paleoproductivity, relative abundance of foraminifera on sediment core PS2837-6. 5 records from Wanninchen. 853 records from Coccolithophorids in surface sediments of the South Atlantic. 388 records from Geometry of coccolith Coccolithus pelagicus in sediment core GIK23062-4. 2 records from Nannofossil abundance of Hole 1-5. 2 records from Nannofossil abundance of Hole 6-50A. 4 records from Nannofossil abundance of Hole 9-81. 134 records from Ostracoda abundance of Hole 48-403. 2 records from Nannofossil abundance of Hole 9-82. 12 records from Nannofossil abundance of Hole 74-528A. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/043-2. 620 records from Lichens of Rocky Seashores. 72 records from Planktic foraminifera counts of sediment core V29-30. 2020 records from (Table 5a) Calcareous nannofossil distribution on ODP Hole 117-722A. 7533 records from Insect (MNHM-IN). 177 records from Antarctic Foraminiferans. 106 records from Antarctic Nemertea. 760 records from Arthropoda specimens of Toyama Science Museum. 29 records from Klimaoasen in Köln. 8 records from Benthic macrofauna abundance of sediment core 12930-017. 13 records from Benthic macrofauna abundance of sediment core 13200-052. 113 records from (Table 1) Abundance of live benthic foraminifera in surface sediments of the Arctic Ocean. 1 records from Bacteria from Penguin Guano, Antarctica. 51 records from (Table 8) Percent distribution of calcareous nannofossils at ODP Hole 125-781A. 141 records from Fig. 7. Relative abundance of ostracod species in composite core JH05. 20 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE255. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 24 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683A, Part II. 1 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE218. 176 records from Larval fish at Helgoland Roads in 2003. 49 records from RSPB - Turtle Dove sightings from research project in East Anglia, 2010. 11737 records from (Appendix II) Planktonic foraminiferal biostratigraphy of ODP Site 113-690. 1473 records from (Appendix 2, Part 1) Distribution of Eocene to Recent benthic foraminifera in ODP Site 113-689. 2501 records from Helmintos parásitos de peces del sureste de México. 1272 records from Registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 174 records from BIRDRACE Bon(n)apartemöwen. 104 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE241. 17 records from (Table 3) Nannofossil occurrence in the Albian of ODP Hole 101-635B. 96 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 113-689B. 12772 records from UAM Invertebrate Collection (Arctos). 1522 records from Ibaraki Nature Museum, Fish collection. 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 1359 records from GEO Biodiversity Day. 6 records from Desmidiaceae Rostock. 603 records from Diatoms from the Vestfold Hills Lakes. 179 records from Reconstruction of surface water temperature of sediment core GIK12379-1, Cape Barbas, North-West Africa (Appendix Tab. 4). 41 records from Altholzparzelle Eilenriede Hannover. 142 records from Birdrace-Alte_Socken-Cuxhaven. 37 records from Occurrence of mammalia relicts at site Villa Seckendorff. 94 records from Occurrence of mammalia relicts at site Krapina. 3653 records from A Dataset of Deep-Sea Fishes Surveyed by Research Vessels in the Waters around Taiwan. 248 records from Range table from benthic foraminifers in ODP Hole 198-1210A. 10 records from Dinoflagellate abundance of Hole 81-552. 829 records from Spring Phytoplankton Assemblages in the Southern Ocean Between Australia and Antarctica (CLIVAR-SR3). 1 records from Abundance of benthos infauna at station PO128/2_284. 40316 records from The Scottish Ornithologists' Club - Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - non-sensitive species. 3 records from Rivulus mahdiaensis, a new killifish from central Guyana (Cyprinodontiformes: Rivulidae).. 3 records from Hornmilben (Oribatida) [pages 213 to 260]. 1060 records from Biodiversidad de grupos funcionales de microorganismos en el Parque Nacional Natural de Los Nevados, Colombia. 240 records from (Table 2) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 123-766A. 13 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-9. 249 records from (Table 2) Distribution of calcareous nannofossils from selected samples of ODP Hole 107-652A. 1188 records from (Table 15) Distribution of planktonic foraminifers in ODP Hole 108-666A. 39 records from (Table 17) Distribution of ostracode species in Core PS51/092-12. 38 records from (Table 7) Pleistocene nannofossil range chart for ODP Hole 134-832A. 156 records from (Table 2) Distribution of some benthic foraminifera in ODP Hole 108-658A. 9900 records from Museo Nacional de Ciencias Naturales. CSIC, Madrid: MNCN-Nemata. 40 records from Palynology of profile Füramoos. 503 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Invertebrados. 12077 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 9 records from Akita Prefectural Museum＋Cephalaspidomorphs Specimens of Akita Prefectural Museum. 159 records from (Table 1) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Site 120-747. 38 records from (Table 1) Chiasmolithus species and intermediate forms of ODP Holes 105-647A and 120-748B. 13 records from Range table from planktonic foraminifers in ODP Hole 172-1055B. 11 records from Foraminifera species abundances from tow TT011_2-MOC57. 1536 records from (Table 5) Distribution of planktonic foraminifera in the latest Pliocene to Holocene section of ODP Hole 149-898A. 2205 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 535 records from Distribution of microorganisms in recent sediments of Kiel Bay. 10741 records from Japan Collection of Microorganisms, RIKEN BioResource Center. 9674 records from Mammal collection of National Museum of Nature and Science. 770 records from Nivå Bay species list, Zealand, Denmark. 4 records from Visual Plants (144.41.33.158) - Plants from Costa Rica; Annette Wolter. 508 records from Guyane_Cacaoyer. 246 records from Rotifers of Macquarie Island. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 109 records from Dreilinden Gymnasium-Schulgelände. 52 records from Occurrence of mammalia relicts at site Zigeunerfels. 11 records from Occurrence of mammalia relicts at site l´Abri Caminade-Ouest. 1018 records from Planktic foraminifera abundance of Hole 9-84. 237 records from Planktic foraminifera abundance of Hole 21-207. 6 records from Range table from planktonic foraminifers in ODP Hole 145-883C. 252 records from Range table from planktonic foraminifers in ODP Hole 155-934A. 525 records from Range table from planktonic foraminifers in ODP Hole 155-941A. 7 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 199 records from Range table from planktonic foraminifers in ODP Hole 167-1012A. 146 records from Range table from planktonic foraminifers in ODP Hole 167-1018A. 3 records from Range table from planktonic foraminifers in ODP Hole 171-1049C. 109 records from Range table from benthic foraminifers in ODP Hole 181-1119B. 2066 records from Range table from benthic foraminifers in ODP Hole 159-959D. 1431 records from (Table 10) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-712A. 15883 records from Canadian Lakes Loon Survey. 466734 records from ECNASAP - East Coast North America Strategic Assessment (OBIS Canada). 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 9810 records from Royal British Columbia Museum Entomology Collection. 46209 records from Herbarium Senckenbergianum Görlitz (GLM). 19903 records from HBGSpermatophyta - Herbarium Hamburgense. 3824 records from Laboratório de Ecologia e Biogeografia de Insetos da Caatinga. 1182 records from Distribution of planktic foraminifera, factor analysis, SST of sediment core PS2498-1. 173 records from Sediment components of core SO82-2. 305 records from Flux data of NU2_trap (Table A1). 1077 records from Percentages of planktonic foraminifera species in sediment core RC24-7. 1399 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-182. 191 records from Foraminifera abundance of sediment core C1960.202. 190 records from Foraminifera abundance of sediment core C1966.435. 1357 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B. 364 records from Langenberger Forst am Ochsenweg/ Niebüll-Leck. 155 records from Bergbaufolgelandschaft am Muldestausee. 134 records from Birdrace-Easy_Birders-Plön. 478 records from Occurrence of mammalia relicts at site Raj Cave. 20 records from Occurrence of mammalia relicts at site Kesslerloch. 500 records from Foraminifera abundance of Hole 48-404. 50 records from Planktic foraminifera abundance of Hole 11-106. 265 records from Planktic foraminifera abundance of Hole 73-521. 320 records from Range table from planktonic foraminifers in ODP Hole 141-863A. 311 records from Range table from planktonic foraminifers in ODP Hole 192-1186A. 3387 records from Sand flies of Eastern Africa. 9 records from Dinoflagellate abundance of Hole 71-513A. 5 records from Two new species of Exallonyx Kieffer (Hymenoptera: Proctotrupidae) from China, with a key to Chinese species.. 400 records from Phytoplankton abundance in surface water in October 1997, Callao, Peru. 33 records from Waldstück am Schullandheim Bad Bederkesa. 96423 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Invertebrate Observation Records other than Lepidoptera. Pre-2010 for Cumbria. 59 records from Main components of radiolarian assemblage at Site 177-1092. 21 records from Sediment fraction analysis and population density of living larger foraminifera in the Persian Gulf (Table 1A, 1B). 763 records from Bisons Collection. 15975 records from condoncollection. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 3027 records from Fungi Collection in BCRC. 13 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Laguna Las Barrancas (Spitznagel, octubre 1999). 3219 records from (Figure 6) Planktonic foraminifera distribution in ODP Hole 130-803D. 10175 records from Seil Natural History Group - SNHG Biological Records Dataset. 395 records from (Appendix C) Total cyst counts, and abundances of Selenopemphix undulata sp. nov. in ODP Site 202-1233. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fregatidae. 167 records from Taxonomic revision of the Palaearctic Tetramorium chefketi species complex (Hymenoptera: Formicidae).. 14317 records from Nematodes collection (IN) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from On the Australian linyphiid spider Alaxchelicera ordinaria Butler, 1932 (Araneae). 32240 records from SP-Bryophyta - Maria Eneyda P. Kauffman Fidalgo. 1770 records from Schmidt Museum of Natural History_Birds. 128 records from (Table 2) Distribution of ebridians and actiniscidians in selected samples from DSDP Hole 90-591. 15 records from Microfossil abundance of Hole 39-358. 240 records from Phytoplankton abundance in surface water in July-August 1996, Pisco, Peru. 2199 records from Plantlife International - Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 18 records from Composition of benthic macrofauna in surface sediments of the east Greenland continental slope (79° N section). 159 records from (Table 1) Distribution of benthic foraminifera in surface sediment of the Elbe estuary. 20 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto20-28. 19 records from Contribution to the Central European Gymnodamaeus species G. barbarossa and G. bicostatus (Acari, Oribatida, Gymnodamaeidae. 8196 records from Formicidae Collection Univesity of Granada. 31 records from Description of a new species of the fish genus Acanthoplesiops Regan (Teleostei: Plesiopidae: Acanthoclininae) from Tonga.. 4001 records from HVAT - Herbário do Vale do Taquari. 2 records from Arthropoden aus südostalpinen Höhlen.. 34 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM4. 1 records from Campylomorphus homalisinus (Elateridae): a new species for Lombardy (Italy), with notes on its ecology, distribution and biogeography. 4436 records from HUEG - Herbário da Universidade Estadual de Goiás. 2379 records from Lichens from Russian Fennoscandia. 699588 records from Royal Botanic Garden Edinburgh Herbarium (E). 3685 records from CNMT - Herbário Centro Norte Mato Grossense. 18959 records from Herbarium Specimens of Bonin and Ryukyu Islands. 3818 records from RSPB - Black-throated Diver annual records in North Scotland, 1834-2010, RSPB, SNH, NTS, SWT, RBBP, FCS, Museum Collections. 20099 records from Arachnida e Myriapoda Museu Nacional (MNRJ ARAC). 1042 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 113 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña noviembre 2006. 3 records from Taxonomy of European Damaeidae (Acari: Oribatida) II. Porobelba weigmanni n. sp. (Oribatida, Damaeidae), from East Slovakia, with comments on other known species of the genus. 760 records from (Figure 1e) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3175GC. 1485 records from (Table T5) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P9-P11. 448 records from Biodiverisity Group, Dept. of Environment, Food and Agriculture,Isle of Man Government - Japanese Knotweed Records in the Isle of Man 1991-2008. 104 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cathartidae. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 12065 records from Tromsø Museum, Bryophytes. 11518 records from Merseyside BioBank - North Merseyside Insects (verified). 496 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 107 records from (Appendix 3) Calcareous nannofossils in ODP Hole 113-690B. 18 records from Survey of the native freshwater opossum shrimp (Mysis relicta) in Ireland. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 29691 records from University of Amsterdam (NL) – Benthos monitoring of the North Sea research database. 7 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 61 records from Artenvielfalt auf der Wiese. 69 records from Entdeckertour am Muldestausee 1/05. 71 records from Birdrace-do_elster_Dortmund. 27 records from Wiese hinter der Schule (Darmstadt). 773 records from Distribution of calcareous foraminifers in sediment core Well 6406/11-1. 83 records from Abundance of living benthic foraminifera in sediment core CD86_02_BC5. 58 records from Abundance of living benthic foraminifera in sediment core CD86_08_BC5. 676 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 94-608 in the North Atlantic. 32 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 141 records from (Table T3) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1138A. 17 records from MVZ Herp Observations (Arctos). 15 records from Inventario de Herpetología Buenos Aires, Tauramena, Casanare. 10512 records from (Table T2) Plankontic foraminifera stratigraphy of ODP Hole 184-1146A. 2707 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 116 records from Concentration of organic-walled dinoflagellate cysts from 116 marine surface samples. 64 records from (Table 2) Planktonic foraminifera species found in sediment trap samples and bottom sediments at Station Vy20-3178. 47499 records from Sphaeroceridae Collection. 1 records from Taenioides kentalleni, a new species of eel goby from Saudi Arabia (Gobiidae: Amblyopinae).. 5872 records from EcoRecord - Beetle (Coleoptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 11 records from (Table AT2) Petrology in point counts of ODP Hole 210-1276A, two ODP Leg 173 sites and DSDP Hole 47-398D. 1246 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 128-798B. 93276 records from Merseyside BioBank - North Merseyside Flowering Plants (verified). 11 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 1095 records from (Figure 3) Distribution of dinoflagellate cysts in the late Albian of DSDP Hole 79-547B. 37 records from Liether Park 2 (LMS), Klasse 6c. 261 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 3509 records from Entocytheridae (Ostracoda) World Database. 51390 records from Scottish Wildlife Trust - The Scottish Squirrel Database. 1 records from Celaeno obsoleta. 216 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 3 records from On two Italian Lithobius species described by Silvestri, with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda, Lithobiida). 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 4 records from New country records of reptiles from Laos. 2 records from On the centipedes (Chilopoda) of the Republic of Macedonia. 1150 records from RSPB - Great Yellow Bumblebee sightings data in the UK, 1990 onwards (RSPB, BBCT, HBRG).. 169 records from HTSAw - Xiloteca do Trópico Semiárido. 2 records from Discothyrea sringerensis (Hymenoptera: Formicidae) a new ant species from India.. 8706 records from NINA botanical collection. 18 records from (Table 3) Foraminiferal species in DSDP Sample 78-541-5-3,19-21. 61468 records from Naturalis National Natural History Museum (NL) – Aves_ Passeriformes. 172 records from Dalbekschlucht. 257 records from Dinocyst occurrences and zonations from IODP Hole 313-M0028A. 100 records from Birdrace-ImmerWiederhopf-Lörrach. 102 records from Industriebrache (Kempen). 36 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 1 records from Waldtag in und um Seelingstädt. 250 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Cetacean data up to current day. 430 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23068-3 in the Norwegian Sea. 53 records from Abundance of living benthic foraminifera in sediment core CD86_09_BC1. 767 records from Scottish Natural Heritage - Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 23 records from Revision of the generic classification of the hawkfishes (Cirrhitidae), with descriptions of three new genera.. 6622 records from The Fossil Fish Collection at the Jura-Museum Eichstätt. 396314 records from British Lichen Society - BLS Lichen Database: English churchyards. 1329 records from Colección de Invertebrados Cenpat (CNP-INV). 645788 records from Norwegian Biodiversity Information Centre - Other datasets. 14172 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 1 records from Nothrus mutilus. 376 records from (Table 1) Distribution of planktonic foraminifera in the Cretaceous succession of DSDP Hole 95-612. 150 records from Birdrace-Ostseevögel-Ostvorpommern. 114 records from Flora. 18 records from Dachterasse Realschule St. Bernhard (Bad Mergentheim). 59 records from Oschenberg, NO von Bayreuth-Laineck. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 24 records from Kaisertal. 7 records from Schulhof A.-Schweitzer Schule (Wetzlar). 1 records from Haslauer Moor. 80 records from Landschaftsschutzgebiet Schmutterwald. 269 records from BIRDRACE Kosmos-Racer. 50 records from BIRDRACE Schwarzstorchbruthöhlen-Initiative Rügen. 63 records from Plasm bearing foraminifera counts of multinet SO118_MSN1266. 139 records from Total foraminifera counts of multinet M42/3_MSN1364. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN649. 136 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1371. 96 records from Total foraminifera counts of trap L2_92_A42. 35 records from Foraminifera species abundances from tow TT011_15-MOC78. 33 records from Planktic foraminifera of sediment core GeoB1402-5. 37 records from Content of coarse fraction and G. menardii in sediment corev V16-202. 11 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 4 records from Microzooplankton abundance and biomass at station NBP97-08-16-3. 5438 records from (Appendix A) Benthic foraminiferal assemblages in sediments of the last 550 kyr of ODP Hole 130-807A from the Ontong Java Plateau, Pacific Ocean. 269 records from Distribution of planktic foraminifera of sediment trap NB6. 128 records from Total foraminifera counts from multinet M31/2_MSN895. 95 records from Total foraminifera counts from multinet M31/2_MSN896. 229 records from Total foraminifera counts of multinet SO117_MSN1245. 159 records from Total foraminifera counts of multinet M21/6_MSN789. 76 records from Total foraminifera counts of multinet M36/2_MSN1107. 233 records from Distribution of planktic foraminifera (125-250 µm) of sediment core GIK23059-3. 22 records from Planktic foraminifera of sediment core GeoB1407-2. 378 records from Size of planktic foraminifera at CTD station PS55/077-1. 9 records from Microzooplankton abundance and biomass at station TT043_4-1. 1 records from Microzooplankton abundance and biomass at station TT050_24-13. 187 records from Butterflies - Irish Wood White Database. 4 records from Sarcodine counts and carbon biomass at station TT008_5-PMOC5. 6 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC5. 3 records from Sarcodine counts and carbon biomass at station TT011_11-CTD142. 6 records from Microzooplankton abundance and biomass at station NBP97-03-12-2. 38 records from Phytoplankton abundance at bottle station A1/52. 36 records from Phytoplankton abundance in surface water in 2000, Ancon, Peru. 50 records from Phytoplankton abundance at several stations in December 2004, Chipana, Chile. 51 records from Microzooplankton abundance measured on water bottle samples at station PS65/545-1. 74297 records from Bees of Ireland. 12 records from Distribution of meiobenthos in sediment core M19_229-2 of the northeastern Atlantic (Table 1). 150 records from Psocodea (Mallophaga) collection of National Museum of Nature and Science. 211 records from Planktic foraminifera counts at CTD station M39/4_404CTD-57. 152 records from Abundance of planktic foraminifera at CTD station M39/4_402CTD-55. 9 records from (Fig. 3) Pollen analysis of the Bosque de Avicennia core. 2 records from Benthic hard-bottom communities abundance at Lilliguapy in 2010. 9 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_214-14. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_4-CTD45. 341 records from Outer Hebrides Biological Recording Project - OHBRP Fungi, Lichens and Lower Plants Dataset - Outer Hebrides. 22 records from Phytoplankton abundance at station Rigel_1_2005-04 in April 2005, Chipana, Chile. 4352 records from (Fig. 3) Stratigraphic ranges of Oligocene planktonic foraminifera and identified biozones in DSDP Hole 77-538A. 87 records from Artenvielfalt des "Grünen Klassenzimmers". 14 records from Nannofossil abundance of Hole 39-353. 2 records from Nannofossil abundance of Hole 30-287. 2 records from Nannofossil abundance of Hole 94-610. 395 records from Ostracode ratios of adult single valves to adult specimens in surface sediment samples from the Persian Gulf (Table 1b). 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-084. 19 records from Meiofauna abundance in sediment core 12930-036. 1409 records from Planktic foraminifera counts of sediment core AB000280. 821 records from Planktic foraminifera counts of sediment core V19-188. 201 records from (Table 2) Relative abundances of calcareous nannofossils in ODP Hole 120-748A. 4722 records from Insect Specimens of Taga Town Museum, Shiga Pref., Japan. 27 records from Phytoplankton abundance at station Rigel_3_2005-05 in May 2005, Chipana, Chile. 56 records from Microzooplankton abundance measured on water bottle samples at station PS65/470-1. 5 records from Distribution of meiobenthos in sediment core M19_216-2 (2) of the northeastern Atlantic (Table 1). 4 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/107-5. 374 records from Ratios of juvenile to total ostracode fauna in surface sediment samples from the Persian Gulf (Table 1b). 10 records from Benthic macrofauna abundance of sediment core 13078-017. 5056 records from IBF Monitoring of Lichens. 6 records from Multivariate discrimination and description of a new species of Tapinoma from the Western United States.. 583 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE262. 4224 records from (Figure 5) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642A. 11981 records from SMNK Mantid Collection. 181 records from (Table 3) Range chart of calcareous nannofossils in ODP Hole 122-763B. 3422 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 4568 records from Base de datos de las regiones prioritarias 113 y 120 en los municipios de Zirándaro y Coahuayutla, (Guerrero). 2299 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 507 records from Hongos hyphomycetes de áreas tropicales y semitropicales del Estado de Veracruz. 173038 records from EPA'S EMAP Database. 3110 records from IFO Filamentous Fungi. 118 records from Lebensraum Stadt und Park. 1677 records from Distribution of planktonic foraminifera in DSDP Hole 31-296 (Table III). 4 records from Zwischen Enz und Schule. 17266 records from Biological Records Centre - Caddisfly (Trichoptera) records from Britain and Ireland to 2003. 8 records from Microfossil abundance of Hole 16-157A. 2 records from Nannofossil abundance of Hole 3-18. 64 records from Nannofossil abundance of Hole 24-231. 22 records from Nannofossil abundance of Hole 94-609B. 2 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms. 28 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 189-1171D. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-098. 121 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 22 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI237. 1013 records from Planktic foraminifera counts of sediment core RE5-034. 115 records from Antarctic Pycnogonids II. 2343 records from (Figure 9) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644A cores 7-12. 3768009 records from Missouri Botanical Garden. 145 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE275. 323 records from (App 5) Relative contents of benthic foraminifera species in Holocene sediments from Core BP01-62/04. 5133 records from (Figure 3) Distribution chart of creatceous planktonic foraminifera of ODP Hole 122-762C. 777 records from (Table 2) Distribution of benthic foraminifera in ODP Hole 120-748A. 243 records from (Table 3) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-749B. 577 records from Estación Experimental de Zonas Áridas (CSIC): EEZA-Herpet. 2792 records from Birds (UWEP-BI). 10049 records from Shellfish (NSMK-MS). 3 records from (Table T1) Lithology and palynomorphs of neogene sediments of ODP Hole 178-1096C. 1574 records from Lepidoptera - SNSD. 14 records from (Table 4b) Abundances of Globorotalia menardii in sediment core INMD-115BX. 40 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 2008 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_2. 2 records from (Supplement Table 5) Percentage cover abundance of plants recorded at the Primary Site on Disko Island. 4012 records from Distribution of dinoflagellate cysts in Eocene-Oligocene sediments of ODP Hole 151-913B. 179 records from Abundance of dinoflagellates and ciliates at time series station Helgoland Roads, North Sea in 2007. 7966 records from MfN - Phasmid Collection. 32 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Invertebrates. 100 records from (Figure 5) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 103-640A. 20 records from (Table 1) Occurrences of ostracodes in ODP Hole 122-761B. 317 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Hole 115-714A. 1617 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_1. 3702 records from Vertebrados terrestres del parque nacional Cañón del Sumidero, Chiapas, México. 1293 records from Base de datos y catálogo de helmintos parásitos de anuros de México. 64 records from Akita Prefectural Museum＋Echinoderms Specimens of Akita Prefectural Museum. 5 records from Bryophyte Collection of Shizuoka Prefecture Museum of Natural History. 95 records from Ibaraki Nature Museum, Amphibians and Reptiles collection. 17355 records from Ibaraki Nature Museum,Lichen collection. 8470 records from (Table 12) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-714A. 34 records from (Table 6) Temporal variations of relative abundance of dead cells (in detritus, conglomerates and associated with Probocsia alata) of total number of living and dead cells of Emiliania huxleyi at Stations AH-2001-B3 and AH-2001-B3A. 15709 records from Museo Nacional de Ciencias Naturales, Colección de Malacología. 172308 records from Naturalis Biodiversity Center (NL) - Coleoptera. 49262 records from SDNHM Birds Collection. 1286 records from Den store paddejagt ("The great amphibian survey"). 1134 records from (Table T11) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P11-P13. 19 records from Nannofossil abundance of Hole 10-90. 1181274 records from Bird tracking - GPS tracking of Lesser Black-backed Gull and Herring Gull breeding at the Belgian coast. 15586 records from Historical quantitative benthos grab samples from the Southern Baltic Sea (EurOBIS). 7664 records from National Institute of Marine Sciences and Technologies - Trawl Surveys (AfrOBIS). 1046 records from NBM Insects. 14285 records from RMCA-HERP. 91633 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1993) (AfrOBIS). 28628 records from Marine invertabrate(Mollusca) specimen database of Osaka Museum of Natural History. 296 records from (Table 2) Lithic grain and foraminifera shell counts in sediment core SU90-08. 1786 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V25-59. 211 records from Planktic foraminifera distribution of sediment core TRI172-22. 336 records from Scottish Natural Heritage - Site Condition Monitoring Records from surveys of lamprey species in five river SACs in Scotland. 156 records from Schulgelände Dientzenhofer-Gymnasium (Bamberg). 239 records from Naturerlebnisraum Koppelsberg. 6 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR50. 48 records from Occurrence of mammalia relicts at site Falkensteinhöhle. 74 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 12 records from Planktic foraminifera abundance of Hole 14-138. 138 records from Planktic foraminifera abundance of Hole 26-250A. 562 records from Foraminifera abundance of Hole 18-176. 813 records from Foraminifera abundance of Hole 64-479. 1787 records from Planktic foraminifera abundance of Hole 80-548. 442 records from Range table from planktonic foraminifers in ODP Hole 155-930C. 15 records from Range table from planktonic foraminifers in ODP Hole 169-1036A. 247 records from Range table from planktonic foraminifers in ODP Hole 171-1050C. 230221 records from UA Herbarium. 12158 records from Gunma Museum of Natural History, Insect Specimen. 1 records from Zetes latirostris. 43 records from Hertfordshire Biological Records Centre - HBRC Wildlife Site Surveys, Hertfordshire. 1110 records from MEXU/Colección Histórica. 551 records from Foraminifera abundance of sediment core CS73-34. 3 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 29 records from (Table 2) Distribution of kummerform and sinistral specimens the planktic foraminifera Contusotruncana contusa in Cretaceous sediments. 269 records from 3. Tag der Artenvielfalt Hockenheim. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station OCTOBER-1994-D2. 38 records from RSPB - Lesser Spotted Woodpecker sample survey in England 2007. 1908 records from (Figure 3) Distribution of planktonic foraminifers in the Cenozoic sediments of DSDP Hole 71-511. 817 records from Planktic foraminifera abundance of Hole 37-332A. 71 records from Range table from planktonic foraminifers in ODP Hole 144-876A. 40 records from Planktic foraminifera abundance of Hole 14-137. 3 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 51 records from (Table 4) Principal component analysis, paleotemperatures and distribution of infaunal benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 156 records from Royal penguin Eudyptes schlegeli census and observations at North Head, Macquarie Island 1952/53. 1 records from Abundance of benthos infauna at station GIK23046-1. 1 records from Nothrus minimus. 153 records from (Appendix H) Benthic foraminifera extinction group species in ODP Hole 172-1055B. 9614 records from University of British Columbia Botanical Garden Collections (UBCBG). 101 records from Nannofossil abundance of Hole 4-30. 4660 records from Distribution of planktonic foraminifera of site GeoB1105. 1033 records from Geochemistry and sedimentology on core PO200/10_8-2. 3 records from Petroscirtes pylei, a new saber-toothed blenny from the Fiji Islands (Teleostei: Blenniidae).. 303 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V27-20. 5 records from Analyses of the recent components of sediment core PS1012-1. 1 records from Arthropoden aus südostalpinen Höhlen.. 2644 records from Planktic foraminifera distribution of sediment core GIK17666-2. 82953 records from Vascular Plants, Observations, Oslo (O). 14 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 108 records from Occurrence of mammalia relicts at site l´Abri du Flageolet I. 11 records from Occurrence of mammalia relicts at site Nörre-Lyngby. 31 records from Occurrence of mammalia relicts at site Sainte-Eulalie. 389 records from Planktic foraminifera abundance of Hole 23-228. 1 records from Planktic foraminifera abundance of Hole 8-72. 71 records from Planktic foraminifera abundance of Hole 2-11A. 651 records from Planktic foraminifera abundance of Hole 9-78. 878 records from Planktic foraminifera abundance of Hole 84-568. 529 records from Range table from planktonic foraminifers in ODP Hole 141-861C. 666 records from Range table from planktonic foraminifers in ODP Hole 171-1051A. 131 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 124 records from Range table from benthic foraminifers in ODP Hole 172-1062A. 262 records from Range table from benthic foraminifers in ODP Hole 189-1170D. 133 records from Nannofossil abundance of Hole 73-519. 496 records from Range table from benthic foraminifers in ODP Hole 145-887A. 15 records from Oberservation of birds at station PS14/159 along 49° West. 59015 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 85449 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 1 records from Conchological Society of Great Britain & Ireland - RISC Non-Native Species Records for Zebra Mussel. 96 records from Guadeloupe_manguier. 26990 records from British Lichen Society - BLS Rare and Threatened Lichen Records: England. 631 records from RSPB - 2008 Twite (Carduelis flavirostris) Breeding Season Survey, Wales RSPB/CCW. 175 records from PSUZC-Rodents Collection. 65326 records from Michigan State University Herbarium Vascular Plants. 185 records from Microbial Culture Collection, National Institute for Environmental Studies. 4312 records from (Table 18) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-593. 403738 records from Marine Conservation Society - Seasearch Marine Surveys. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 425 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 27 records from Análisis ecológico de la mastofauna en la parte alta del Rio Güangui. 147 records from Notes on Shore Flies (Diptera: Ephydridae) from Finland and north-western Russia. 191 records from Chinese species of egg-parasitoids of the genera Oxyscelio Kieffer, Heptascelio Kieffer and Platyscelio Kieffer (Hymenoptera: Platygastridae s. l., Scelioninae). 4555 records from Colección de referencia de otolitos, Instituto de Ciencias del Mar-CSIC. 850 records from (Table 3) Distribution of benthic foraminifers from ODP Hole 134-828A. 1 records from New species of Lathrolestes Förster (Hymenoptera: Ichneumonidae) from Côte d’Ivoire. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 834 records from Diptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2731 records from Collection du Musée d'Histoire Naturelle de Nice. 37 records from A brief review of Triplophysa (Cypriniformes: Balitoridae) species from the Tarim Basin in Xinjiang, China, with description of a new species.. 11268 records from Aphidoidea Collection. 415 records from Dinoflagellate cysts from the Upper Hauterivian (Cretaceous) of a claystone-marlstone succession in the clay-pit Frielingen. 5306601 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 106 records from Irish Wire Weed (Sargassum muticum) Database. 490 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 171B-1051A sediments. 175 records from NPWS Pine Marten database. 6 records from Die Milben in der Zoologischen Staatssammlung München. Teil 10. Überfamilie Crotonioidea (I). 347088 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 6422 records from Ájtte. 11591 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments. 24 records from Sphodromantis viridis (Forskal, 1775): New for Portugal and new records of the rare and small mantids Apteromantis aptera (Fuente, 1894) and Perlamantis allibertii Guérin-Méneville, 1843 in the country (Mantodea: Mantidae and Amorphoscelidae). 1168 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 2377 records from Dutch Mammal Society (NL) - Mouse observations of life trap studies extracted from historic reports. 53985 records from BioMar - LIFE project. 20870 records from HUEM - Herbário da Universidade Estadual de Maringá. 1 records from Oribates gilvipes. 7509 records from Perot Museum of Nature and Science. 99463 records from NPL collections. 3945 records from TTRS Ornithology. 632 records from MVZ Hildebrand Collection (Arctos). 33 records from (Table 6) Distribution and abundance of calcareous-nannoplankton species in the Cretaceous sediments of DSDP Hole 62-466. 114203 records from UTA Herpetology. 5 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Pipridae. 192 records from (Table 2) Relative abundance of selceted benthic foraminifera taxa of DSDP Hole 93-605. 196 records from (Figure 4) Distribution of dinoflagellates in ODP Hole 129-802A. 1 records from Red list project inventory, bryophytes. 51 records from Six new species of ants (Insecta: Hymenoptera: Formicidae) from Egypt.. 146382 records from Swedish Board of Fisheries (Fiskeriverket) - Institute of Coastal Research. 30 records from (Table 1) Carbonate constituents and quartz in the sand-sized fraction in Mississippi Fan sediments, DSDP Hole 96-615. 8629 records from National Taiwan University. 4 records from Schulbiotop und Brigach (Villingen). 1462 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Flora Vascular Amenazada. 157 records from BIRDRACE Rheinische Wasserrallen. 77 records from Plasm bearing foraminifera counts of multinet M21/2_MSN644. 133 records from Abundance of planktic foraminifera at CTD station PS55/018. 892 records from Dinoflagellate cyst counts on sediment core ABC26. 1 records from Microzooplankton abundance and biomass at station TT050_25-4. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-02-2. 10 records from Phytoplankton abundance at station Rigel_5_2005-02 in Febraury 2005, Chipana, Chile. 5 records from Nannofossil abundance of Hole 18-175. 16 records from Diatom abundance measured on water bottle samples at station PS58/088-4. 18 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001I. 9 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 48 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1209A. 122409 records from UAM Mammal Collection (Arctos). 251744 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 19309 records from Mammal collection, Natural History Museum, University of Oslo. 94 records from Birdrace-Resopal_Altkreis_Dieburg-Team-Darmstadt/Dieburg. 104 records from Außengelände KITA "Mäuseburg" Waldkirchen. 46 records from 8c. 318 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 1666 records from Occurrence of planktic foraminifera in Pliocene to Holocene sediments of DSDP Hole 81-552A in the North Atlantic (Appendix 2). 14 records from Plasm bearing foraminifera counts from multinet M31/2_MSN893. 90 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 44 records from Plasm bearing foraminifera counts of multinet M21/5_MSN735. 43 records from Total foraminifera counts of trap L2_96_62. 2 records from Planktic foraminifera counts of multinet PS2616-5. 28 records from Content of coarse fraction and G. menardii in sediment corev V25-59. 61 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/546-19. 137 records from Abundance of planktic foraminifera at CTD station PS55/077-1. 3900 records from Dinoflagellate cysts counts of sediment core MD95-2042. 2 records from Microzooplankton abundance and biomass at station TT050_15-3. 3381 records from (Table 10B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-588A. 38 records from Inventario de Murciélagos Buena Vista, Jaramá, Yopal, Casanare. 97 records from Natur-Erlebnis-Kindergarten Waldkirchen/Erzgebirge. 127 records from Birdrace-Alb_Donaumoos_Kompetänzteam-Alb-Donau-Kreis. 106 records from NSG Forst Zinna-Jüterbog-Keilberg. 126 records from BIRDRACE Die Schwenker-Birder. 45 records from Reusaer Wald. 141 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC2-L, size fraction >150 µm. 21 records from Foraminifera species abundances from tow TT007_15-MOC23. 29 records from Content of coarse fraction and G. menardii in sediment corev V26-101. 321 records from Calcareous dionoflagellate cysts from surface sediments. 66 records from Calcareous dinoflagellates nominated in grain fraction < 20 µm. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_1-CTD14. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_7-CTD88. 118 records from Phytoplankton abundance at Station Sechin_EP2 in 2002, Casma, Peru. 119 records from Distribution of planktonic foraminifera of sediment core SH1972_16. 1055 records from Macro benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 233 records from annex3. 218 records from Distribution of main calcareous nannofossils at Site 1093. 67 records from Abundance of coccosphere-units of sediment core GIK23071-2. 52 records from Nanoplankton abundance at station GeoB2017-4. 39 records from Ostracoda abundance of Hole 24-238. 15 records from Nannofossil abundance of Hole 1-3. 45006 records from Fungi field notes, Oslo (O). 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-12-1. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-28-3. 9 records from Phytoplankton abundance at station Casma_2003-01-30_1, Casma, Peru. 4 records from Abundance of nematoda in sediment profile M3/1_031 from the Iberian deep sea basin (Table 5). 670 records from Bulau. 149 records from Bayerische Donau - Neu Ulm. 776 records from Composition of the coccolith flora in sediment core K708-007. 26 records from Ostracoda abundance of Hole 13-132. 2 records from Nannofossil abundance of Hole 9-79A. 27 records from Composition of the medium silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-020. 264 records from Planktic foraminifera counts of sediment core RC12-339. 1096683 records from Nationaal Herbarium Nederland. 2210 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 20 records from (Table 4) Pleistocene to Miocene ostracodes from ODP Hole 104-643A. 162 records from (Table 5) Distribution of calcareous nannofossils from selected samples of ODP Hole 107-655A. 176 records from (Table 1) Distribution of main species of planktonic foraminifers in Core AMK21-2168, Woodlark Basin. 67112 records from Ehime University Coleoptera Collection. 6188 records from (Figure 1) Range chart of planktonic foraminiferal species at ODP Hole 107-654A. 531 records from Artenvielfalt der Nordsee - Bremerhaven (Dorum-Neufeld). 47 records from Spandau HBO. 125 records from Range table from ostracoda in ODP Hole 143-866B. 144 records from Relative abundance of N. pachyderma sinistral in sediment core PS1243-1. 256 records from Planktic foraminifera counts of sediment core V16-20. 349 records from Planktic foraminifera counts of sediment core V20-170. 1336 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 2509 records from Colección de Oligoquetos Acuáticos de la UPV/EHU. 8345 records from Colección Nacional de Equinodermos Mexicanos (ICMyL-DF, UNAM). 6256 records from Colección Ictiológica del Río Bravo en México (UANL). 3 records from Grünfläche Forckenbeckplatz. 25439 records from Birds (JNHM-BI). 52359 records from Iziko. 34 records from Two new species of Pseudecheneis, rheophilic catfishes (Teleostei: Sisoridae) from Nepal.. 1148 records from Southern Ocean Ostracoda (except Halocypridina). 225 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE262. 24 records from (Table 6) Distribution of Pleistocene to late Pliocene nannofossils in ODP Hole 108-660A. 27 records from (Table 12) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-688A. 243 records from (Table 1) Oligocene benthic foraminifers abundance in ODP Hole 124-767B. 2267 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 68 records from (Table 2) Palynomorph concentrations in ODP Hole 105-647A samples. 492 records from Pliocene/Pleistocene benthic foraminiferal abundances from hole KR9912PC4. 364 records from Dornwanger Moos. 8 records from Diatom abundance measured on water bottle samples at station PS58/041-2. 1513 records from A geographic distribution database of Mononychellus mites (Acari: Tetranychidae) on cassava (Manihot esculenta). 78 records from Planktic foraminifera counts of sediment core A180-73. 27 records from Feuchtbiotop Otto-Hahn-Gymnasium. 500 records from Plant (HBBG-PL). 17841 records from Mycology Herbarium, Trondheim (TRH). 1000 records from Colección de los peces nativos de Sonora. 9 records from (Table 2) Macrobenthos on the floor of the West Bay of the Furugelm Island, Sea of Japan. 23315 records from Gwaii Haanas Invertebrates (OBIS Canada). 24286 records from Ross A. Layberry Observations. 30150 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 5224 records from Insect Specimens of Omogo Mountain Museum. 21794 records from Bryophyte specimens database of Mr. Tsutomu Kodama collection, Osaka museum of Natural History. 81037 records from Museum of Zoology, University of Navarra. 323 records from CNAN/Pseudoscorpiones. 224 records from Weinberge und angrenzende Felsflächen (Drieschen) in Hatzenport/Terrassenmosel. 16 records from Phytoplankton abundance during Professor Siedlecki cruise PSied90/1. 1355 records from Planktic foraminifera abundance of Hole 18-173. 22 records from Planktic foraminifera abundance of Hole 51-417. 15 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0003A. 73 records from Benthic foraminifera abundance of Hole 80-550. 1 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/554-2. 12 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-1. 107 records from Bases de datos de Poliquetos pelágicos del Golfo de México y Mar Caribe mexicano. 1240 records from Diversidad y conservación de orquídeas de la región de Chimalapa, Oaxaca, México. 900 records from Manual ilustrado de las orquídeas silvestres del estado de Morelos. 397 records from Taxonomía e inventario de cianofitas del orden chroococcales (Cyanophyceae). 3635 records from Raw counts of dinoflagellate cysts in several IODP and DSDP holes. 1268 records from (Appendix A) Ostracod taxa from IODP Site 306-U1314. 6628 records from Database on Forest Disturbances in Europe. 22817 records from Floristische Kartierung Österreichs - Mapping the Flora of Austria. 72625 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1990) (AfrOBIS). 2015 records from Distribution of planktic foraminifera, factor analysis, SST of sediment core PS2495-3. 638 records from Geochemistry and sedimentology on core PO200/10_21-1. 2243 records from Stable isotopes, diversity and composition of foraminifera in sediment core GeoB3004-1. 522 records from Relative abundance of planktonic foraminifera in sediment core L-198. 87075 records from Banc de dades de biodiversitat de Catalunya-ArtroCat. 126031 records from Mosquito Occurrence Dataset. 2330 records from (Appendix C) Distribution of benthic foraminifera in surface sediments from the Chatham Rise. 582 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1995-1999. Part 3. 25 records from Heavy minerals of sediment core PS2792-5. 367 records from ARKO. 4 records from Description of lithologic section units of IODP Hole 325-M0034A. 330046 records from Broedvogels - Atlas of the breeding birds in Flanders 2000-2002. 1665 records from (Table 11) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 603 records from Polish Arctic Marine Programme (EurOBIS). 7926 records from NBM birds. 1429 records from Morano and Cardoso: AraIb. 320 records from Planktic foraminifera assemblage in sediment core GIK11944-1. 162843 records from Biodiversitätsdatenbank des Landes Salzburg. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1422-1. 84571 records from Repatriación de datos del Herbario de Arizona (ARIZ). 302015 records from University of Alberta Entomology Collection (UASM). 224 records from Bizzenbach-Aue im Bizzenbachtal (Wehrheim/Taunus). 12 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB01 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 21 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100260. 64 records from Occurrence of mammalia relicts at site Lespezi-Lutarie. 12 records from Occurrence of mammalia relicts at site Trafalgar Square. 52 records from Occurrence of mammalia relicts at site Goyet Cave 3. 151 records from Planktic foraminifera abundance of Hole 74-527. 215 records from Foraminifera abundance of Hole 64-480. 12 records from Planktic foraminifera abundance of Hole 2-9. 149 records from Planktic foraminifera abundance of Hole 29-282. 21 records from Hypostomus rhantos (Siluriformes: Loricariidae), a new species from southern Venezuela.. 871 records from Benthic foraminiferal assemblages (dead), surface data. 13 records from Collection Reptilia fossil SMF. 46 records from Effects of varying food-availability on ecology and distribution of smallest benthic organisms in sediments of the arctic Fram Strait during POLARSTERN cruise ARK-XV/2. 101 records from (Table S1d) Measured tomographic parameters for Oridorsalis umbonatus during ETM-2 for ODP Holes 208-1263C and 208-1262A. 193 records from The velvet spiders: an atlas of the Eresidae (Arachnida, Araneae). 24492 records from NCSM Invertebrates Collection. 3137 records from Herbarium - Las Cruces Biological Station. 19 records from New Linyphiidae spiders associated with playas in the Southern High Plains (Llano Estacado) of Texas (Arachnida: Araneae). 311768 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 149 records from (Appendix A) Palynofacies raw counts of DSDP Hole 38-338. 146809 records from OHN. 4745 records from Herbier A. Le Grand (BOUM). 17447 records from Swedish Board of Fisheries (Fiskeriverket) - National Register of Survey testfishing. 2 records from Stadtrand Berlin - Altglienicke/ Was krabbelt auf unserem Abenteuerspielplatz?. 57 records from Schulgarten Janusz-Korczak-Realschule. 17 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD63. 7 records from Microzooplankton abundance and biomass at station NBP97-03-10-10. 40 records from Occurrence of mammalia relicts at site Cueva Millan. 42 records from Occurrence of mammalia relicts at site Wildenscheuer Cave. 172 records from Foraminifera abundance of Hole 59-448A. 331 records from Range table from planktonic foraminifers in ODP Hole 141-859A. 54 records from Range table from planktonic foraminifers in ODP Hole 141-862A. 542 records from Range table from planktonic foraminifers in ODP Hole 182-1127B. 535 records from Benthic foraminifera abundance of Hole 73-522. 1788 records from Benthic foraminifera abundance of Hole 84-568, Part 2. 1741 records from Benthic foraminifera abundance of Hole 84-570, Part 1. 15 records from Range table from benthic foraminifers in ODP Hole 189-1172D. 115 records from Range table from benthic foraminifers in ODP Hole 149-899B. 701 records from Range table from benthic foraminifers in ODP Hole 151-913B. 30024 records from Mammal specimens. 3719 records from (Figure 4) Stratigraphic distribution of planktonic foraminifera in DSDP Hole 93-604. 24 records from Range table from benthic foraminifers in ODP Hole 192-1185B. 355 records from Dinoflagellate abundance of Hole 94-607. 308 records from Phytoplankton abundance in surface water in November 1997, Chimbote, Peru. 73043 records from North Carolina State Museum of Natural Sciences Fishes Collection. 84 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction < 20µm. 8527 records from HSU Wildlife Birds. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 1387 records from (Figure 6) Dinoflagellate cyst measured on sediment core AI07-12G. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 448 records from Range table from benthic foraminifers in ODP Hole 192-1183A. 56 records from Range table from benthic foraminifers in ODP Hole 144-874A. 204 records from Range table from benthic foraminifers in ODP Hole 171-1051A. 163 records from Dinoflagellate cysts of ODP Hole 189-1172D. 185502 records from Entomology Division, Yale Peabody Museum. 833709 records from AMNH Bird Collection. 1549 records from Mushroom - Higher Fungi (KIDR-MR). 249 records from Herbarium of the Department of Natural Forests (Forest Research Institute) - Lichens. 233 records from Briòfits d'Andorra. 29367 records from Geographic distribution of dinoflagellate cysts in surface sediments. 6062 records from Lichens of Knyszyn Forest. 27 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 67 records from Inventario Murciélagos Finca Naranjito, Aracal, Yopal, Casanare. 1 records from Zetes flavipes. 19356 records from Hymenoptera. 2 records from Nannofossil abundance of Hole 6-57A. 228 records from (Tab. 8) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 79-547B, Mazagan Basin west of Morocco. 22 records from Dinoflagellate abundance of Hole 14-144. 13 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (verified). 3946 records from EcoRecord - Amphibian records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 1 records from Arthropoden aus südostalpinen Höhlen.. 29488 records from Animal Sound Archive. 28277 records from Herts Bird Club - Hertfordshire Breeding Bird Atlas : 1988-1992. 7771 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Platyhelminthes. 2167 records from Otter Survey of Ireland 1982. 3509 records from Entocytheridae (Ostracoda) World Database. 7848 records from Lichen specimen database of Faurie collection. 76124 records from Lichen field notes, Oslo (O). 2 records from High-resolution X-ray computed tomography of an extant new Donuea (Araneae: Liocranidae) species in Madagascan copal. 581 records from Collection scientifique et pédagogique de l'Ecole Normale Supérieure de Lyon. 875 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Sandwood Estate during 1998 â 2006.. 2 records from Nannofossil abundance of Hole 1-4. 107 records from RSPB - Crested tit wintering survey in the UK, 1992-1995 (RSPB). 351058 records from Staffordshire Ecological Record - SER Species-based Surveys. 5583 records from All observations extracted from the Flora of Northumberland and Durham 1831. 9552 records from Countryside Council for Wales - UK Biodiversity Action Plan Invertebrate Data for Wales. 794 records from Irish Deer Database. 12 records from (Table 1) Parameters of zoobenthos in the Kemskaya Guba littoral area. 2443 records from Cnidaria MZS. 3525 records from Countryside Council for Wales - Important Welsh Bat Roosts Database (BATSITES-WALES). 93 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cotingidae. 84 records from (Table 3) Minerals, and calcareous and siliceous fossil residues from DSDP Hole 93-603. 23300 records from Central African Plants. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Formicariidae. 1390 records from (Appendix 1) Calcareous nannofossils in ODP Hole 119-738B. 57 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 73514 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 277 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 1 records from Zetes longiusculus. 32 records from A review of the subfamily Acaenitinae Förster, 1869 (Hymenoptera, Ichneumonidae) from Ukrainian Carpathians. 108313 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 131148 records from Fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 108 records from (Table 3) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-844B. 30 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto1-10. 10030 records from Free-living marine Nematodes from San Julián bay (Santa Cruz, Argentine), 2009.. 1710 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 1387717 records from Fishbase. 13086 records from Collection of Coleoptera. 52 records from Isotope tracer experiment: meiofauna counts. 9248 records from UAM Fish Collection (Arctos). 540 records from Streamlining the use of BOLD specimen data to record species distributions: a case study with ten Nearctic species of Microgastrinae (Hymenoptera: Braconidae). 1803 records from Flora of tanzania. 777 records from INRA-Versailles Arabidopsis natural variants. 9792 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection. 27988 records from Inventaire National du Patrimoine Naturel : Loup en France. 1 records from Oribates badius. 564 records from Streamlining the use of BOLD specimen data to record species distributions: a case study with ten Nearctic species of Microgastrinae (Hymenoptera: Braconidae). 1376 records from Vertical distribution of nannofossils in the section of DSDP Site 72-516. 724 records from University of Amsterdam (NL) - Páramo vegetation research, Talamanca Cordillera, Costa Rica. 91 records from Foraminifera assemblage in surface sediments of the Skagerrak/Kattegat area. 607 records from Líquens d'Andorra. 51 records from Sea Algae. 74 records from (Table 3) Abundance of benthic foraminifera and ostracoda in bottom sediments from the Ashadze-1 Hydrothermal Field. 42 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 24 records from (Table 1) Stage of the lemming cycle and nesting parameters of the greater snow geese between 1996-2005, Bylot Island. 38200 records from Herbario Universidad de Antioquia (HUA). 179 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cuculidae. 111682 records from British Phycological Society - Seaweed data for Great Britain and Ireland. 192273 records from Field Museum of Natural History (Zoology) Mammal Collection. 246 records from CaCO3, biogenic opal, TOC, and microfossil observations of sediment core MR06-04_PC23A. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 1 records from Nothrus biciliatus. 233 records from Föhrenried (Fronreute und Baindt). 68 records from Schulhof der Astrid-Lindgren-Schule (Elmshorn). 155 records from Birdrace-Usedommeln-Ostvorpommern. 482 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 124 records from Total foraminifera counts of multinet M10/2_MSN317. 34 records from Total foraminifera counts of multinet M21/4_MSN715. 62 records from Plasm bearing foraminifera counts of multinet M21/5_MSN728. 132 records from Abundance of planktic foraminifera at CTD station PS55/080-1. 384 records from (Supplement Table) Individual body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 40 records from Inventario de Herpetología en el Área Sujeta a Acuerdos de Conservación Voluntaria Quebrada Aguazula, Rincón del Soldado, Yopal. 38 records from Fourteen new species of Pseudisobrachium (Hymenoptera, Bethylidae) from Atlantic rain forest of Espírito Santo, Brazil.. 766 records from Antarctic Porifera database from the Spanish benthic expeditions: Bentart, Gebrap and Ciemar. 1 records from Nothrus pigerrimus. 45 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 5 records from (Table 2) Osmium isotope ratios and Re-Os element content for cleaned and uncleande foraminifera of ODP Hole 121-758A. 1138 records from (Table T2) Benthic foraminfera stratigraphy of ODP Hole 199-1220B sediments. 4 records from Pollen analysis of sediment profile PLU01 from Plussee. 800 records from PSUZC-Amphibians Collection. 62015 records from Atlas of Iberian water beetles (ESACIB database). 89 records from Collection Crustacea - PUM. 40481 records from Biological Records Centre - Soldier Beetle and Jewel Beetle (Coleoptera; Cantharoidea and Buprestoidea) records for Britain and Ireland to 2000. 33 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto57-65. 22 records from Dellwiger Bach (Dortmund). 103 records from Schwanseepark (87645 Schwangau). 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 20 records from Lerchenauer Baggersee (München). 15339 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 78 records from BIRDRACE leucorhö statt logorrhö. 1 records from Microzooplankton abundance and biomass at station TT050_17-5. 7 records from Kryptolebias sepia n. sp. (Actinopterygii: Cyprinodontiformes: Rivulidae), a new killifish from the Tapanahony River drainage in southeast Surinam.. 14605 records from DMNS Mammal Collection (Arctos). 72 records from Birdrace-Buteo2DO-Dortmund. 63 records from Hochschule Zittau/Görlitz. 207 records from Biosphäre Bliesgau. 42 records from Feuchtwiese Grüne Mitte, Klasse 5a. 43 records from Assemblage of living benthic foraminifera in sediment core CD145_55808#3, 63-150 µm. 205 records from Total foraminifera counts from multinet SO119_MSN1281. 149 records from Plasm bearing foraminifera counts from M35/1_MSN1046. 102 records from Plasm bearing foraminifera counts of multinet M12/3_MSN559. 138 records from Plasm bearing foraminifera counts of multinet M21/2_MSN652. 44 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/580-12. 1998 records from Institut Botanic de Barcelona, BC-Lichenotheca. 24 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD22. 2303 records from Planktic foraminifera abundance in per cent of Hole PRAD1-2. 71 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/367-1. 62 records from Artenvielfalt in der Kinderakademie im RFZ. 265 records from Luderbusch. 102 records from Listhof und Umgebung. 216 records from Museu de Ciències Naturals de Barcelona: MCNB-ZG. 43 records from MfN - Fossil invertebrates Ib. 2 records from MfN - Glacial erratics. 10 records from MfN - Fossil plants II. 3 records from Nannofossil abundance of Hole 10-93. 32356 records from Actualización de la base de datos del Atlas Mastozoológico de México. 1098 records from Mushroom in North Korean (KIDR-MR). 39 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 30-63 µm. 10 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 30-63 µm fraction. 147 records from Total foraminifera counts from multinet M31/2_MSN889. 143 records from Total foraminifera counts of multinet M12/3_MSN535. 115 records from Plasm bearing foraminifera counts of multinet M21/1_MSN614. 51 records from Total foraminifera counts of multinet M27/2_MSN884. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 65 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 1 records from Nothrus scaliger. 24 records from Content of coarse fraction and G. menardii in sediment corev V25-43. 13 records from Content of coarse fraction and G. menardii in sediment corev V25-49. 10 records from Microzooplankton abundance and biomass at station TT045_19-3. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_2-CTD26. 3 records from Sarcodine counts and carbon biomass at station TT011_4-CTD46. 510 records from Alterra (NL) - Microarthropods inventory in a range of forests. 3 records from Phytoplankton abundance at station Rigel_2_2005-07 in July 2005, Chipana, Chile. 8 records from Phytoplankton abundance at station Casma_2003-01-30_2, Casma, Peru. 25 records from Phytoplankton abundance at station Sechin_2003-11-25_2, Casma, Peru. 34 records from Microzooplankton abundance measured on water bottle samples at station PS65/424-3. 78 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1b. 1395 records from Birds - Wild Birds (KIDR-BI). 1070 records from (Table 1) Distribution of agglutinated benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 87 records from Stable isotopes measured on Ammonia beccarii from sediment core GIK12523-1. 4 records from Sarcodine counts and carbon biomass at station TT008_5-PMOC3. 7 records from Phytoplankton abundance at station Casma_2003-02-15_2, Casma, Peru. 7 records from Phytoplankton abundance at station Casma_2003-02-27_2, Casma, Peru. 11431 records from Herp Specimens. 344 records from Butterberg, Dardesheim. 52 records from Nannofossil abundance in sediment core PS1297-4. 13 records from Benthic macrofauna abundance of sediment core 13200-081. 421 records from Planktic foraminifera counts of sediment core RC09-162. 149 records from A multi-proxy investigation of sediment core GeoB7165-1 ~60 km offshore Concepción. 64 records from (Table 4) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Calabianca section. 6342 records from (Table 2) Plio-Pleistocene benthic foraminifera of ODP Hole 107-654A. 2093 records from Elasmobranquios del Golfo de Tehuantepec, litoral chiapaneco. 1092 records from (Table 5) Oligocene planktonic foraminifera of DSDP Hole 29-277. 5183 records from DAO Herbarium Type Specimens. 2698297 records from Eremaea. 2267 records from Relative abundance of organic-walled dinoflagellate cysts in surface sediments. 189 records from (Fig. 10) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 41-367 in the North Atlantic. 29 records from Phytoplankton abundance at station Rigel_2_2005-05 in May 2005, Chipana, Chile. 121 records from (Table 2, 3) Macro- and meiofaunal specimens abundance, organic carbon content and analysis of coarse clasts of box core samples from the North Pacific Ocean. 127 records from Distribution of planktonic foraminifera of sediment core SH1972_2. 41884 records from Museu Paraense Emilio Goeldi - Ornithology Collection. 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 27 records from Ostracoda abundance of Hole 42-376. 115 records from Nannofossil abundance of Hole 29-279A. 4 records from Ostracoda abundance of Hole 56-435. 18 records from Nannofossil abundance of Hole 29-279. 2 records from Nannofossil abundance of Hole 20-199. 16 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/012-5. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 63 records from Matter enrichment of the macrofauna community of MAC station 12930-005. 9660 records from (Table 3) Ranges of upper Eocene Holocene planktonic foraminifera in ODP Hole 119-744A. 214 records from (Appendix C) Analyses of the benthic foraminifer assemblage at ODP Hole 112-679D. 3023 records from Flora y datos básicos para la evaluación de las actividades apícola y forestal en tres áreas focales del corredor Sian Ka'an-Calakmul. 1001 records from Ictiofauna insular del medio y bajo Golfo de California. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán. 11 records from Description of lithologic section units of IODP Hole 325-M0055A. 48 records from Planktic foraminifera assemblage in sediment core GIK17725-1. 8 records from Zoobenthos in surface sediments in the Yalta Bay. 267 records from Phytoplankton abundance and species composition in the North Balearic Sea in March 2003. 22 records from Coleoptera identified from the Hornchurch Marshes site, Dagenham, London. 83 records from Naturpark Kottenforst-Ville 16.6.09. 73 records from Coccolith counts of multinet SO119_MSN1278. 66 records from Range table from ostracoda in ODP Hole 151-910D. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-075. 40 records from Meiofauna abundance in sediment core 13368-019. 262 records from Coiling ratios of Pulleniatina spp. in sediments from DSDP Hole 16-157. 3362 records from Coimbra Collection of Algae. 374843 records from BSBI tetrad data for Ireland. 17 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Trogonidae. 241 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 357 records from Sistematización de la Colección Paleontológica de la Facultad de Ingeniería, UNAM. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 261 records from Foraminifera distribution of sediment core MD81-BC15. 52 records from Meiofauna abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 41 records from Nannofossil abundance of Hole 26-251A. 45 records from Coccoliths in sediment core PS1532-9. 85 records from (Table 5) Abundance of selected helicoliths at DSDP Site 82-563 in the North Atlantic. 15 records from Benthic macrofauna abundance of sediment core 13077-093. 39 records from New records for Albania based on taxa from the Prespa National Park. 1949 records from (Table 4b) Calcareous nannofossil distribution on ODP Hole 117-721B. 945 records from (Appendix D) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748C. 6909 records from Herbario del Departamento de Biología Vegetal (Botánica) de la Universidad de La Laguna, Tenerife (TFC). 15166 records from Insect Collection of Yokosuka City Museum. 43 records from Antarctic and sub-Antarctic Lophogastrida occurrences. 1 records from On the Chilopoda from Turkey. 67 records from (Table 5) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 375 records from (Table 3) Relative abundances of benthic foraminifera in ODP Hole 105-646A. 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 39 records from (Table 1) Distribution of foraminiferal tests in recent sediments of interior seas of Malay Archipelago. 940 records from Mastofauna de la vertiente occidental (oeste) del Parque Nacional Pico de Orizaba, Puebla (Fase 1). 7443 records from Free-living marine Nematodes from San Antonio bay (Río Negro, Argentine) 2009.. 2750 records from Botanical specimens database of Mr. Jiro Ito collection, Shizuoka Prefecture Museum of Natural History. 6 records from Description of lithologic section units of IODP Hole 325-M0054B. 156 records from (Table 1) Occurrence of bottom invertebrates in the Canary upwelling area. 750 records from (Table 20) Benthic foraminifera in early Miocene sediments of DSDP Hole 90-594. 25955 records from Freshwater fish collection. 21333 records from Coleccion de Herpetologia, MZFC-UNAM. 98709 records from USU-UTC Specimen Database. 17 records from Visual Plants (144.41.33.158) - Private collection of Vindas Jorge, Costa Rica. 22 records from Sediment properties of core PLG95B_06BOXG. 535 records from Percentages of planktonic foraminifera species in sediment core V30-41. 123 records from 4. GEO-Tag in Eberbach. 118 records from Natur aus zweiter Hand am Muldestausee. 245 records from Schulbiotop Dr.-Gustav-Schickedanz-Hauptschule (Fürth). 104 records from Urwald 1 (Bad Waldsee). 176 records from Renaturierung Werse (Innenbereich Beckum). 94 records from Birdrace-Filz_Fledermäuse-Münster. 1 records from Occurrence of mammalia relicts at site Egtved. 595 records from Planktic foraminifera abundance of Hole 37-335. 6 records from Type specimen data for Nicrophorus efferens Sikes & Mousseau. 196 records from Range table from planktonic foraminifers in ODP Hole 162-986D. 7 records from Range table from planktonic foraminifers in ODP Hole 169-1035C. 12 records from Range table from planktonic foraminifers in ODP Hole 175-1076C. 29 records from Range table from planktonic foraminifers in ODP Hole 175-1079A. 16 records from Range table from planktonic foraminifers in ODP Hole 183-1138A. 868 records from (Table 3) Planktic foraminiferal abundance in Oligocene to Early Pliocene sediments of ODP Hole 177-1090D on the Agulhas Ridge, South Atlantic. 21 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (2000m section). 7020 records from (Table 2) Distribution and abundance of selected planktonic foraminifera of the Pliocene DSDP Hole 41-369A. 29 records from Potential indicator species of climate changes occurring in Québec, Part 1: the small brown lacewing fly Micromus posticus (Walker) (Neuroptera: Hemerobiidae). 635 records from Bermuda Atlantic Time-series Study Zooplankton Census. 26841 records from MSUM Ichthyology and Herpetology Collections. 1901 records from The University of Hong Kong Herbarium. 4948 records from (Table T1) Abundance of planktic forminifera in ODP Site 177-1090. 2504 records from Collections data on ecology of bottom animal of the Southern ocean. 156 records from Blumenrather Heide / Virneburg. 29 records from Hemmerder Schelk (Unna). 12 records from Abundance of microplankton from bottle APRIL-2000-K4. 22 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 21 records from (Table 1) Dinoflagellate species and specimen abundance in Maastrichtian sediments of the Bass River Section in the southern New Jersey. 9 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB4. 4 records from Occurrence of mammalia relicts at site Klausennische. 433 records from Planktic foraminifera abundance of Hole 22-214. 1059 records from Planktic foraminifera abundance of Hole 15-148. 3988 records from Planktic foraminifera abundance of Hole 26-254. 20 records from Review of the Camponotus aureopilus species-group (Hymenoptera, Formicidae), including a second Camponotus with a metapleural gland.. 1592 records from (Table 8) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-584. 226 records from Planktic foraminifera abundance of Hole 32-313. 1049 records from Planktic foraminifera abundance of Hole 84-570. 50682 records from CZE National PGR Inventory. 417 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 20 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1995-D2. 234 records from Occurrence of mammalia relicts at site Pestera Cioarei. 30 records from Occurrence of mammalia relicts at site Stematia. 68 records from Planktic foraminifera abundance of Hole 4-29B. 598 records from Foraminifera abundance of Hole 60-459B. 65 records from Planktic foraminifera abundance of Hole 11-106B. 12 records from Range table from planktonic foraminifers in ODP Hole 169-1038F. 498 records from Dinoflagellate abundance of Hole 94-611C. 4263 records from Collection Porifera SMF. 1 records from Celaeno coccinea. 934 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Biodiversity Action Group Japanese Knotweed Survey. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 58327 records from Inventaire National du Patrimoine Naturel : Fichier communal des ongulés. 34 records from Revision of the Bahamian cave-fishes of the genus Lucifuga (Ophidiiformes, Bythitidae), with description of a new species from islands on the Little Bahama Bank.. 330 records from RSPB - Red-Throated Diver National Survey in Britain in 2006 - 5km square summary (SCARABBS). 27812 records from Collection of saproxylic and xylobiont Beetles. 1 records from Cheiloneurus flaccus (Walker, 1847) (Hymenoptera: Encyrtidae), new to New Zealand. 264 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Picidae. 3761 records from Atlas of the Amphibians and Reptiles of Poland. 1238 records from Insect Collection (CeStuBio). 160 records from Scottish Natural Heritage - Distribution of Scottish wildcats (Felis silvestris) in Scotland (2006-2008) â database extract (breeding and non-breeding records). 10137 records from Royal Horticultural Society - RHS lily beetle (Lilioceris lilii) monitoring. 9216 records from Inventaire National du Patrimoine Naturel : Crustacés Décapodes de France. 3 records from Selenops muehlmannorum spec. nov. from Southern Laos (Araneae: Selenopidae). 192 records from Range table from planktonic foraminifers in ODP Hole 146-891B. 15575 records from (Appendix A) Planktonic foraminifer abundance and ranges of ODP Hole 165-999A sediments. 88 records from Range table from planktonic foraminifers in ODP Hole 167-1021B. 11328 records from Colección Nacional de Entomología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 63 records from Range table from benthic foraminifers in ODP Hole 172-1062B. 18 records from Range table from benthic foraminifers in ODP Hole 144-871A. 37 records from Range table from benthic foraminifers in ODP Hole 182-1128D. 1024 records from Benthic foraminiferal assemblages (living), surface data. 157 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera of surface sediment off Morocco (Table 6). 64 records from Sedimentology and radiolarian distribution in latest Miocene to Recent sediments of ODP Hole 175-1084A from the Benguela Upwelling System, South Atlantic. 573 records from (Table 1) Absolute abundances of Eocene to Oligocene planktonic foraminifera in ODP Hole 135-841B. 526 records from FernsDarwinCore. 69 records from Distribution of Miocene benthic foraminifera of sediment core CRP-1 (Fig. 1). 84986 records from NINA Vanndata fisk. 1 records from Chilopoden und Diplopoden aus Jugoslavischen Höhlen. 1159 records from Countryside Council for Wales - Bat Roosts Database - North East Wales. 36 records from Pseudolaguvia ferula, a new species of sisoroid catfish (Teleostei: Erethistidae) from India.. 16 records from A review of the gobiid genus Akko (Teleostei: Gobiidae) with description of a new species.. 135 records from Collection Pisces - KAUMM. 717 records from Alterra (NL) - Microarthropods inventory in militairy zone Leusderheide. 44561 records from Flora of the Stołowe Mts.. 1680 records from Distribution of reworked planktic foraminifera in Neogene sediments of core CLINO from the Great Bahama Bank (Table 1). 675 records from Benthic foraminifera and algae abundance of Hole 81-553A. 1 records from Benthic foraminifera abundance of Hole 96-624. 3 records from Range table from benthic foraminifers in ODP Hole 178-1095A. 150 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 191 records from Range table from benthic foraminifers in ODP Hole 198-1211A. 208 records from Range table from benthic foraminifers in ODP Hole 144-875C. 4051 records from Homoptera. 666 records from (Tab. 4) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-105, Bahama Lower Continental Rise Hill. 3 records from Microfossil abundance of Hole 21-208. 565 records from Marine palynomorph abundance estimates of sediment core CRP-2A (Fig. 2). 216 records from Naturpark Drömling. 214 records from NSG Haunestausee, Hauneteiche. 1 records from Carabodes coriaceus. 496 records from Outer Hebrides Biological Recording Project - OHBRP Invertebrates (except insects) Dataset - Outer Hebrides. 10121 records from Arachnologie - SMNG. 87324 records from Ouellet-Robert entomological collection (QMOR). 193 records from Herbario IES San Isidoro de Sevilla. 60 records from (Table T1) Diatom biostratigraphy of ODP Hole 183-1140A. 908 records from (Appendix A1) Planktonic foraminifera of ODP Hole 157-951A. 3664 records from Primera caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 4 records from Seodaemun Museum of Natural History Fossil. 24 records from A new genus and two new species of congrid eels (Teleostei: Anguilliformes: Congridae) from the Indo-West Pacific, with a redescription and osteology of Chiloconger dentatus.. 181724 records from ArtenFinder. 1 records from On the Chilopoda from Turkey. 149 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 49 records from Total foraminifera counts of multinet FCA97C_MSN1345. 1297 records from Dinoflagellate assemblage in surface sediments of the South Atlantic. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-10-12. 16 records from Benthic macrofauna abundance of sediment core 13200-047. 1 records from Sungei Buloh - Mangrovenwald. 1992 records from Plant (GFEI-PL). 757 records from Sistemática y biogeografía del género Xenosaurus (Squamata: xenosauridae). 503 records from Inventario fitopatológico de las especies vegetales dominantes en la región de Zapotitlán de las Salinas, Pue.. 354 records from Microfossil abundance of Hole 35-323. 81 records from Range table from planktonic foraminifers in ODP Hole 180-1109D. 18 records from (Tab. 2) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 1-4, Blake-Bahama Basin. 892 records from Weevils of Wales and England. 7 records from Kaulsdorf. 12 records from (Table IV) Abundance of isopoda families during RSS James Clark Ross cruise JR144. 142691 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 21760 records from CUMV Mammal Collection (Arctos). 1245 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 344 records from Meiofaunal abundance in sediments obtained during Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 562 records from A preliminary checklist of the ants (Hymenoptera: Formicidae) of Iran.. 968 records from TTRS Mammals. 49362 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 4438 records from ISE - Herbário ISE. 7 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Melanopareiidae. 367 records from Longhorn and buprestid beetles (Coleoptera: Cerambycidae, Buprestidae) of the forest-steppe “Bielinek” reserve and its surroundings. 51803 records from CESJ - Herbário Leopoldo Krieger. 1476 records from Harvestmen_of_French_Guiana. 1658 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 155 records from Bammentaler Duft- und Heilkräutergarten. 31 records from Regenwasserabfangbecken. 112 records from Kaniswall/ Gosener Wiesen an der Spree. 102 records from BIRDRACE Willi goes Birding. 17 records from Hydrolagus mccoskeri sp. nov., a new species of chimaeroid fish from the Galápagos Islands (Holocephali: Chimaeriformes: Chimaeridae).. 53 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 8 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 30-63 µm. 76 records from Faunal assemblage of sediment core GS7603-10. 113 records from Total foraminifera counts from multinet M31/2_MSN890. 134 records from Total foraminifera counts from multinet SO119_MSN1284. 156 records from Total foraminifera counts of multinet M10/2_MSN261. 111 records from Total foraminifera counts of multinet M12/3_MSN557. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 5 records from Arthropoden aus südostalpinen Höhlen.. 10 records from Merodoras nheco, new genus and species from Rio Paraguay basin, Brazil (Siluriformes, Doradidae), and nomination of the new subfamily Astrodoradinae.. 9788 records from SANT-Lich. 1 records from A new species of the genus Sinanapis (Araneae: Anapidae) from Lam Dong province, southern Vietnam.. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 8 records from Five new species of the damselfish genus Chromis (Perciformes: Labroidei: Pomacentridae) from deep coral reefs in the tropical western Pacific.. 924 records from (Table 15) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-592. 10255 records from Araneae Collection. 1 records from Hoplophora crinita. 314 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 181 records from Alien Species in Poland - Animals. 16 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas III. Suctobelbella alloenasuta n. sp. und Suctobelbella messneri n. sp. sowie die bisher aus der DDR bekannten Arten der nasalis-subtrigona-Gruppe (Suctobelbidae). 161 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-852B. 59 records from Im Bauerngarten. 122 records from Birdrace-Hügelland-Mainz/Bingen. 23 records from Tümpel Schulbiologiezentrum. 11 records from Kirschfest (Grundschule Heldrungen) / Kirschberg Oberheldrungen. 255 records from Colecciones Zoológicas de la Universidad de León, Colección de Bivalvos. 21548 records from Benthic foraminifera abundance of ODP Site 184-1143. 77 records from Total foraminifera counts from M35/1_MSN1075. 142 records from Total foraminifera counts of multinet M21/3_MSN675. 82 records from Plasm bearing foraminifera counts of multinet M27/2_MSN883. 41695 records from AIMS LTM Fish (OBIS Australia). 808 records from Greater Manchester Ecology Unit - Distribution of Great Crested Newts in Greater Manchester. 30 records from Specimens from India at the University Museum at the University of Bergen. 16696 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Fungi and Lichen Observation Records. Pre-2010 for Cumbria.. 325 records from Triebesbach (Zeulenroda-Triebes). 193 records from Gelände des Schulzentrums am Himmelsbarg. 369 records from BIRDRACE Havelland. 18 records from Landschaftsschutzgebiet Buchhorst2. 2040 records from Perthshire Black Grouse Study Group (PBGSG) - Black Grouse annual lek counts in Perthshire 1990-2009 (Perthshire Black Grouse Study Group). 101 records from (Table 4a) Downcore distribution of live benthic foraminifera of sediment core SW_3a, California continental borderland. 14 records from Distribution of planktic foraminifera of sediment core GIK23062-1 at stadium 5.5. 125 records from Abundance of planktic foraminifera at CTD station PS55/082-1. 29 records from Biological data measured on water bottle sampels at station AT_II-119/5_38-5. 139641 records from Countryside Council for Wales - Marine data from Countryside Council for Wales (CCW) Technical Support (Research & Monitoring) Contracts, Wales. 6 records from Phytoplankton abundance in surface water in 2005, Ancon, Peru. 7 records from Distribution of meiobenthos in sediment core M23_133 of the northeastern Atlantic (Table 1). 292 records from (Table A1) Calcareous nannofossil of the Middle Cenomanian Event in ODP Site 207-1260. 34 records from annex4. 88 records from Upper Aptian Niveau Kilian range chart of nannofossils in SE France. 69 records from Coccolith counts of multinet SO119_MSN1295. 108 records from Planktic foraminifera counts of sediment core RC08-39. 734 records from Mammals (NSMK-MM). 842 records from Marine specimens of Misaki Marine Biological Station, School of Science, University of Tokyo. 68 records from Total foraminifera counts of multinet M21/4_MSN696. 51 records from Total foraminifera counts of multinet M21/4_MSN712. 48 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1197. 26 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1368. 52 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1382. 237 records from (Appendix B) Abundance of calcareous dinoflagellates of sediment core GeoB1105-4. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_11-CTD137. 15 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_13-CTD162. 11 records from Phytoplankton abundance at stations off Paita in August 1995, Piura, Peru. 84 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 72-516F. 32 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2157-3. 2905 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-9. 42 records from Stadtwald Heide. 15382 records from Bird Specimens in the Museum of Nature and Human Activities, Hyogo, Japan. 225 records from Nannofossil abundance of Hole 15-154A. 127 records from Nannofossil abundance of Hole 78-541. 3 records from Nannofossil abundance of Hole 7-63. 128 records from Nannofossil abundance of Hole 4-25. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/045-2. 526 records from (Table 1) Relative abundances of calcareous nannofossils in ODP Hole 115-711A. 175 records from Neißetal. 45 records from Wasser-Lernort Nettemündung. 104 records from Antarctic Parborlasia corrugatus. 251821 records from Countryside Council for Wales - Phase 2 Lowland Grassland Survey of Wales. 96 records from Plasm bearing foraminifera counts of multinet M21/2_MSN650. 98 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1381. 13 records from Content of coarse fraction and G. menardii in sediment corev V25-52. 45 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/544-6. 2 records from Typhlichthys eigenmanni Charlton, 1933, an available name for a blind cavefish (Teleostei: Amblyopsidae), differentiated on the basis of characters of the central nervous system.. 331 records from Size of planktic foraminifera at CTD station PS55/082-1. 55232 records from Herbario de la Universidad de Granada: GDA. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_7-CTD82. 1 records from Microplankton counts and carbon biomass at station TT007_5-CTD53. 3 records from Sarcodine counts and carbon biomass at station TT007_5-CTD53. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5. 128 records from Phytoplankton abundance at station CD47_2805C#5. 16 records from Phytoplankton abundance at station Rigel_1_2005-02 in Febraury 2005, Chipana, Chile. 6 records from Phytoplankton abundance at station Rigel_1_2005-03 in March 2005, Chipana, Chile. 21 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 7 records from Distribution of meiobenthos in sediment core M23_199 (2) of the northeastern Atlantic (Table 1). 14 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/323-1. 50 records from NABU-Fläche am Bösselhausener Weg. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_10-CTD124. 51 records from Coccoliths in sediment core PS1295-4. 4 records from Nannofossil abundance of Hole 16-156. 47 records from Physical properties, geochemistry and ostracoda abundance of sediment core Lz1080. 7 records from Phytoplankton abundance measured on water bottle samples at station PS65/466-2. 14108 records from Rådgivende Biologer. 67 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 85 records from Meiofauna abundance in sediment core 13077-014. 5415 records from Coleopteran specimens of Iwate Prefectural Museum. 49 records from NSG Hellbachtal. 1368 records from Bird Collection of Yokosuka City Museum. 9762 records from Amphibian and Reptile (NSMK-AR). 5995 records from Insect (HUNM-IN). 8336 records from Birds (GMBO-BI). 14 records from (Table 4b) Abundances of Globorotalia menardii in sediment core INMD-111BX. 100 records from (Table 5) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the Lesches en Diois section. 1281 records from (Figure 2) Distribution chart of creatceous planktonic foraminifera of ODP Hole 122-761B. 1134 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 350 records from (Table 3b) Foraminiferal distribution chart of ODP Hole 122-761B. 79 records from (Appendix E) Analyses of the benthic foraminifer assemblage at ODP Hole 112-681B. 1090 records from Diversidad biológica y conservación del ecosistema de los perros de la pradera (Cymomys ludovicianus) en México. 381 records from Estudio taxonómico de moluscos terrestres y dulceacuícolas de la región maya de México I. Reserva de la Biosfera Pantanos de Centla. 3 records from Akita Prefectural Museum＋Millipedes Specimens of Akita Prefectural Museum. 6 records from MfN - Micropaleontology. 132 records from Distribution of planktonic foraminifers in ODP Hole 104-642A (Table 2). 249 records from (Table 1) Relative abundance of selected benthic foraminifera in ODP Hole 104-644A. 4858 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Berkshire Meadows Survey 1984-87 (as held by Thames Valley Environmental Records Centre). 1805 records from (Table 2) Occurrence of Oligocene to Pleistocene benthic foraminifers in ODP Site 121-756. 1152 records from (Table 1) Occurrence of Oligocene to Pleistocene benthic foraminifers in ODP Hole 121-754A. 50 records from (Table 4) Abundances of dinoflagellates in DSDP Hole 81-552A. 320 records from Myxomycetes collection of the University of Eastern Finland. 481 records from (Table 3f) Foraminiferal distribution chart of petroleum well Montara-2. 2070 records from (Table 4) Plio-Pleistocene benthic foraminifera of ODP Hole 107-652A. 1222 records from Ichneumonidae (Hymenoptera) de la reserva de la biosfera El Cielo, Tamaulipas. 858 records from Diversidad y distribución de las comunidades de fitoplancton de ríos y lagunas del volcán San Martín de la reserva de la biósfera Los Tuxtlas. 2000 records from Biodiversidad de los crustáceos dulceacuícolas del centro de Nuevo León y noroeste de Tamaulipas. 5125 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 8089 records from Los díptera hematófagos y taxa relacionados de dos áreas protegidas del estado de Yucatán, México (Insecta). 177 records from Echinodermata specimens of Kuroshio Biological Research Foundation. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 435 records from (Table 4) Distribution of calcareous nannofossils from selected samples of ODP Hole 107-654A. 3478 records from Especies de peces introducidas en aguas continentales de México. Catálogo y manuscrito. 14194 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN Fase 1: Estado de México, Hidalgo, San Luis Potosí y Tlaxcala. 5080 records from Riqueza específica, distribución y abundancia de aves terrestres y marinas en Isla San José, Golfo de California, Baja California Sur, México. 87929 records from Herbario de la Universidad de Sevilla, SEV. 81105 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1998) (AfrOBIS). 2042 records from Butterflies and Skippers of Alberta Project. 42 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Florian Werner. 238 records from Ophion scutellaris species group specimen data. 2431 records from Foraminifera, sedimentological parameters and sea surface temperature and salinity calculated on core SO82_5-2. 433 records from Foraminifera abundance of sediment core BS78-12. 3 records from Analyses of the recent components of sediment core PS1010-1. 2 records from Occurrence of mammalia relicts at site Grotte du Bichon. 6950 records from (Table 1) Occurrence of selected planktonic foraminifers, other microfossils, and lithologic components at DSDP Hole 96-619. 1100 records from Foraminifera abundance of Hole 64-478. 6403 records from Planktic foraminifera abundance of Hole 47-397. 28 records from Planktic foraminifera abundance of Hole 94-610D. 132 records from Range table from planktonic foraminifers in ODP Hole 177-1089A. 108 records from Range table from planktonic foraminifers in ODP Hole 180-1114A. 284 records from Localities for the arachnid genus Acuclavella (Opiliones, Ceratolasmatidae). 15663 records from Leiner-Herbar Konstanz. 14885 records from Ontario Breeding Bird Atlas 1981-1985. 2618 records from MAR-ECO (EurOBIS). 48114 records from MMNH Museum Bird Collection. 1655 records from Water Colours of Fungi by Konrad Schieferdecker at the Botanische Staatssammlung München. 6187 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 1535 records from Mushroom Collection in BCRC. 275 records from Foraminifera abundance of sediment core C1960.199. 28 records from Occurrence of mammalia relicts at site Bedburg-Königshoven. 10 records from Occurrence of mammalia relicts at site Aveley. 617 records from Planktic foraminifera abundance of Hole 23-223. 542 records from Planktic foraminifera abundance of Hole 18-175. 518 records from Foraminifera abundance of Hole 21-208. 29 records from Range table from planktonic foraminifers in ODP Hole 146-888A. 56 records from Range table from planktonic foraminifers in ODP Hole 167-1010C. 23 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 179 records from Relative abundances of benthic foraminifera in surface sediments (Table A3). 56685 records from MISS_DC_01MAR2006. 2 records from Abundance of benthos infauna at station GIK23042-2. 12 records from Early succession in benthic hard bottom communities in Kongsfjorden, Svalbard - abundance. 14319 records from Irish Records from the Fungal Records Database of Britain and Ireland. 4943 records from Collembola Collection. 52 records from A new species of Cordyligaster Macquart, reared from caterpillars in Area de Conservacion Guanacaste, northwestern Costa Rica. 1197 records from Hertfordshire Biological Records Centre - Hertfordshire Urban Surveys (incomplete). 3 records from (Table 5) Organic matter contents and paleoproductivities at DSDP Site 75-532. 2458 records from Colección de Ictiología. 43242 records from Bentos collection of the Museum of Nature and Human Activities, Hyogo. 7472 records from Collection Bernstein - SMF. 31157 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2003) (AfrOBIS). 1321 records from Priest Pot species list, Cumbria, Britain. 265 records from CNIN/Mantodea. 1 records from Schulman's Neotropical Adelobotrys database. 111905 records from Herbarium Willing. 200187 records from inatura - Erlebnis Naturschau Dornbirn. 18192 records from Plant Specimens of The Shimane Nature Museum of Mt. Sanbe. 2430 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 12113 records from Distribution of planktic foraminifers and SST of sediment core GIK15637-1. 251 records from Micoteca da Universidade do Minho. 186 records from Schulhof Goethe-Gymnasium (Emmendingen). 80 records from Streuobstwiese/Naturerlebnisraum Koppelsberg (Plön). 134 records from Birdrace-Raumpatrouille_Oriolus-Münster. 1968 records from (Appendix B) Distribution of planktonic foraminifera at DSDP Hole 72-518. 66 records from Occurrence of mammalia relicts at site Malerfels_I. 105 records from Occurrence of mammalia relicts at site l´Abri du Pont d´Ambon. 11 records from Occurrence of mammalia relicts at site Stockstadt. 26 records from Occurrence of mammalia relicts at site Predmosti. 3 records from Occurrence of mammalia relicts at site Sesselfelsgrotte. 1289 records from Neogene palynomorpha from site 93-603, part 2. 150 records from Planktic foraminifera abundance of Hole 31-299. 44 records from Planktic foraminifera abundance of Hole 51-417A. 3 records from Range table from planktonic foraminifers in ODP Hole 139-856E. 83 records from Range table from planktonic foraminifers in ODP Hole 139-858A. 807 records from (Table 4) Planktonic foraminifer abundance of ODP Hole 162-981A. 105 records from Plasm bearing foraminifera counts of multinet M21/5_MSN731. 328 records from Range table from planktonic foraminifers in ODP Hole 170-1040C. 286 records from Inventory of the Heteroptera (Insecta: Hemiptera) in Komaba Campus of the University of Tokyo, a highly urbanized area in Japan. 1 records from Dinoflagellate abundance of Hole 38-336. 384 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 9050 records from Relative abundance of benthic foraminifera in sediment core M5/2_KL15. 632 records from (Appendix A1) Relative abundances of benthic foraminifera and stable carbon isotope ratios of Nuttallides truempyi at the Paleocene-Eocene thermal maximum in ODP Hole 198-1209B in the central Pacific. 624 records from Quirópteros del Parque Natural Regional El Vínculo y su zona de amortiguación (Buga, Valle del Cauca, Colombia). 1 records from Abundance of benthos infauna at station GIK23013-2. 7 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 1794 records from Herbarium BSG Lichenes. 7868 records from Inventaire National du Patrimoine Naturel : Insectes Coléoptères Saproxylophages de France. 1 records from Oribates coracinus. 121 records from A second update to the checklist of Finnish long-legged flies (Diptera: Dolichopodidae), with a re-evaluation of the status of Hydrophorus callosoma Frey, 1915. 122 records from A second update to the checklist of Finnish long-legged flies (Diptera: Dolichopodidae), with a re-evaluation of the status of Hydrophorus callosoma Frey, 1915. 477418 records from Fungi (S). 1 records from Arthropoden aus südostalpinen Höhlen.. 140 records from Three new percid fishes (Percidae: Percina) from the Mobile Basin drainage of Alabama, Georgia, and Tennessee.. 352 records from Scottish Natural Heritage - Recovery of the medicinal leech Hirudo medicinalis in Scotland - Phase II. 2 records from Beiträge zur Kenntnis bulgarischen Chilopoden. Teil V. Das Genus Polybothrus. 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 48 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1366. 102 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1380. 62 records from Range table from benthic foraminifers in ODP Hole 174-1071C. 2 records from Range table from benthic foraminifers in ODP Hole 139-858B. 65 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 107 records from Specimens from India at the Natural History Museum at the University of Oslo (NHM-UiO). 2423 records from SANT-Bryo. 8 records from (Table 1) Proportion of Toxoplasma gondii seropositive arctic foxes (Alopex lagopus) by age group and geographic area. 5042 records from Tracheophyta collection of Biodiversity Center of Japan, Ministry of Environment. 4475 records from Coleoptera collection (EC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3597 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209C sediments. 191 records from Herpetofauna laguna El Tinije. 5729 records from Alterra (NL) - Entomofauna inventory in cattle grazed dune grassland. 1 records from (Table 4) Thecosomata in ODP Hole 134-831A. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 124 records from (Appendix A1) Cenomanian benthic foraminifera of ODP Hole 207-1258A. 15956 records from Algae (S). 48 records from Tardigrada collection of National Museum of Nature and Science. 94 records from (Fig. 3) Inter-core correlation of Ca/Fe ratios and magnetic susceptibility supported by IRD and N. pachyderma (sin) of sediment core GeoB11035-1. 37 records from Berlin - Treptower Park / Karpfenteich. 35 records from Gym Freyung. 1294 records from Global Butterfly Information System (GloBIS). 1 records from Occurrence of mammalia relicts at site Neasham. 4 records from A new species of Pachyurus Agassiz 1831 (Teleostei: Perciformes: Sciaenidae) from the Río Napo basin, Eastern Ecuador.. 5612 records from Marine Biological Association - 2005-Ongoing United Kingdom MarLIN Shore Thing timed search results. 375 records from Phthiraptera. 3 records from Revision of the ant genus Perissomyrmex with notes on the phylogeny of the tribe Myrmecinini.. 12 records from Six new, unusually small ants of the genus Leptomyrmex (Hymenoptera: Formicidae).. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 132 records from (Table T2) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049B. 108 records from (Table 5) Live benthic foraminifera in sediment core SO130-236MC. 423 records from (Table 2) Benthic foraminiferal distribution at ODP Hole 127-795B. 38841 records from Herbier de Strasbourg. 28 records from The land crab Johngarthia planata (Stimpson, 1860) (Crustacea, Brachyura, Gecarcinidae) colonizes human-dominated ecosystems in the continental mainland coast of Mexico. 19451 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 122 records from Stever. 48 records from Trockenrasen bei Dörndorf. 40 records from Tiere und Pflanzen um uns herum !. 61 records from BIRDRACE Baumläufer. 120 records from BIRDRACE Ornis im Einsatz. 77 records from VFD-RP: Taunus: Mähweide Dehe. 112 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction 63-150 µm. 190 records from Assemblage of living benthic foraminifera in sediment core GeoB3706-3. 152 records from Plasm bearing foraminifera counts of multinet SO118_MSN1252. 133 records from Total foraminifera counts of multinet M10/2_MSN265. 53 records from Total foraminifera counts of multinet M21/5_MSN735. 131 records from Total foraminifera counts of multinet M21/6_MSN788. 20 records from (Table 2) Counts of live (stained) benthic foraminifera from stations in the northern Gulf of California. 3904981 records from FlorKart - FlorenKartierung Gefaesspflanzen. 6 records from A new Savignia from Cretan caves (Araneae: Linyphiidae). 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 77 records from Terrestrial gastropods of Srebarna Nature Reserve, North-Eastern Bulgaria (Gastropoda). 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 183 records from Westerwälder U
Keywords: GBIF; biodiversity; species occurrences